Metal–organic frameworks as next-generation preservation platforms for postharvest fruits and vegetables: Gas regulation, antimicrobial control, bioactive delivery, and intelligent monitoring - Hao Shi; Min Zhang; Arun S. Mujumdar; Luming Rui (Postharvest Biology and Technology, 2027)

Comparative analysis of product distribution and kinetics in steam gasification of rice straw under atmospheric and pressurized conditions - Deming Zhang; Mingshui Ma; Hao Bai; Rui Zhou; Zhenguo Li; Yiqing Yao (Biomass and Bioenergy, 2026)

L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Role of glutamine in promoting the proliferation and chondrogenic differentiation of ATDC5 cells: based on transcriptomic analysis - Rui-hao Zhang; Wen-huan Yuan; Ze-long Wang; Qi-rui Yang; Yi Sun; Quan-nian Shao; Wen-ji Wang; Jing Wang (Molecular Biology Reports, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Model tests on the evolution characteristics and aggravation effects of seepage erosion in shield tunnels under train vibration - Hui-Hao Chen; Dong-Mei Zhang; Xiao-Chuang Xie; Xue-Liang Zhang; Si-Rui Chen; Jie Yang (Tunnelling and Underground Space Technology, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Organic amendments induce crop-specific soil biotic homogenization associated with SOC sequestration: Evidence from a 35-year intercropping experiment - Guizong Zhang; Jiudong Zhang; Rui-Peng Yu; Hao Yang; Xingguo Bao; Wenju Liang; Qi Li; Long Li (Soil and Tillage Research, 2026)

Negative regulation of seed germination in Medicago truncatula by the lncRNA MtCIR1 under salt stress is associated with alternative splicing - Rui Tian; Xiaohan Sun; Mingui Zhao; Wen-Hao Zhang (Plant Science, 2026)

Association of combined exposure to polycyclic aromatic hydrocarbons, BTX and metals with metabolic syndrome risk - Xiaoyu Hao; Xiangkai Zhao; Zhiguang Gu; Bin Yang; Di Zhang; Rui Zhao; Xu Guo; Zhe Cheng; Gang Wang; Xiaohui Li; Junfeng Zhao; Zhiheng Li; et al. (Environmental Pollution, 2026)

Managing nitrate pollution in mixed land-use watersheds: source attribution and removal revealed by isotopes and 15N pairing - Jian Zhang; Hao Jiang; Yanping Li; Wenshi Zhang; Wenlu Lan; Junlin Shu; Xin Luo; Rui Zhang; Ke Pan (Ecological Engineering, 2026)

Built-in electric field for synergistically regulating electronic structure and interfacial hydrogen-bond network toward ampere-level current anion exchange membrane water electrolysis - Yujie Liang; Xinyu Lao; Jiaying Zhang; Hao Feng; Rui Min; Jingjing Wang; Yingying Zheng; Jiaqi Pan; Chaorong Li; Jun Cao (Chemical Engineering Journal, 2026)

Design of a biomimetic walking wheel inspired by reindeer hoof morphology and its snow-terrain locomotion performance - Kaixiang Chen; Rui Zhang; Mingxi Yu; Huailiang Wang; Hao Pang; Lige Wen (Cold Regions Science and Technology, 2026)

Organic amendment quality and quantity govern microbial necromass contributions to soil carbon sequestration: a meta-analysis - Jiaqi Hao; Mengdi Wang; Yiting Chen; Hui Xia; Hailin Zhang; Pete Smith; Yapeng Jiao; Binbin Cao; Yan Gao; Jianglan Shi; Xiangtian Meng; Rui Yin; et al. (Soil Biology and Biochemistry, 2026)

Electronic, optical and mechanical properties, and photocatalytic water splitting of Janus ZrHfCO2 under biaxial strain: First-principles prediction - Rui-Wen Yan; Hao Zhang; Xiao-Hong Li; Rui-Zhou Zhang; Hong-Ling Cui (Journal of Environmental Chemical Engineering, 2026)

Transient geomorphic processes revealed by luminescence sensitivity of Yellow River terrace sediments - Ya Liu; Zheng-Hao Gu; Jia-Fu Zhang; Xue Rui; Yu-Jie Guo; Song-Xi Du; Yu-He Shen; Qing-Hao Ma (Geomorphology, 2026)

Beyond flavor: dietary vanillyl alcohol, a D₂ receptor antagonist promoting sleep - Lijing Zhang; Yujie Yang; Dongmei Yang; Richard Ward; Zhenshuai Hu; Hao Chen; Mengli Lan; Cheng Xiang; Su An; Jiameng Dai; Ying Zhu; Xianrun Sun; et al. (Food Research International, 2026)

Yield advantage in wide strip intercropping: Border-row effects and adding a third crop in double relay intercropping - Hao Yang; Huai-Ying Ma; Yi-Wen Zhao; Jiu-Dong Zhang; Gui-Zong Zhang; Jia-Kang Lu; Ya-Xian Huang; Xing-Guo Bao; Rui-Peng Yu; Wopke van der Werf; Long Li (Field Crops Research, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Smart responsive heterojunction hydrogel for synergistic therapy to promote drug-resistant diabetic wound repair and tissue regeneration - Zhiyang Ren; Rui Liu; Zhifu Liu; Xiaohan Zhang; Tianxin Wang; Lulu Chu; Wenjie Wang; Hao Wang (Chemical Engineering Journal, 2026)

Flower-like PtCuTe nanozymes for synergistic photothermal and Fenton-like antibacterial therapy in infected wound healing - Ding Luo; Ji Cheng; Hao Zhang; Rui Liu; Hanjing Lu; Xudong Liu; Yuji Weng; Yunjun Zhang; Jianli Liu; Xiangyan Meng; Jinghua Li; Qi Lv; et al. (Chemical Engineering Journal, 2026)

Transparent, bio-based dielectric films with ultrahigh breakdown strength fabricated from hydrogen-bonded cellulose acetate and tannic acid for energy storage - Rui Luo; Xin-rui Xiao; Zhe-hao Kang; Chao-qun Wu; Ting Huang; Nan Zhang; Yong Wang (Carbohydrate Polymers, 2026)

Synergistic Effect of Indole-3-Acetic Acid and Homogeneously Dispersed Ulva prolifera-Derived Carbon Quantum Dots in Enhancing CO2 Fixation, Biomass Production, and Macromolecules in Chlorella vulgaris - Chuande Liu; Hao Chen; Yuye Jiang; Rui Zhang; Linzhu Peng; Shuang Wang; Esakkimuthu Sivakumar (Bioresource Technology, 2026)

Sustainable valorization of agricultural waste into high-value aromatics via an integrated chemo-enzymatic strategy - Fang Gao; Shike She; Yaxin Wang; Mengyao Hao; Ming Wu; Yacheng Cao; Dong Zhu; Liping Shi; Liang Zhang; Rui Zhu (Biomass and Bioenergy, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Bone biochar as a bifunctional catalyst for sustainable co-removal of nitrate and phosphate in constructed wetlands - Tao Liu; Hao Qin; Sihan Li; Gongliang Zhang; Rui Wang; Yi Sun; Haihua Wu; Yuxin Zeng; Yi Chen (Water Research, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Divergent effects of biodegradable and conventional microplastics on denitrification in soils: Mechanisms governing N₂O emission and product stoichiometry - Hao Zhang; Xiao Li; Minhang Zhu; Rui Wang; Jinbo Zhang; Christoph Müller; Rui Jiang (Journal of Hazardous Materials, 2026)

Environmentally relevant imidacloprid exposure elicits hippocampal microglial apoptosis via JNK-FOXO3 pathway: Implication for latent central neurotoxicity - Xinyi Wen; Meiyan Li; Zhongyuan Zhang; Jingwen Wang; Hao Hu; Weihong Wang; Jing Jin; Kairong Wang; Jian Sun; Rui Zhang (Journal of Hazardous Materials, 2026)

Lactobacillus helveticus MB2-1 powders prepared using different drying strategies reshape dominant intermolecular interaction patterns and structural network formation during fermentation of coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Yibo Shi; Xiaotong Hao; Shiyuan Feng; Chunling Meng; Jiamin Xu; Di Yu; Tao Lin; Kai Ma; Changliang Zhang; Mingsheng Dong; et al. (Food and Bioproducts Processing, 2026)

Natural resource accounting for urban ecosystem: A case study in Central China based on the System of Environmental-Economic Accounting - Hao Zhang; Yanwen Wang; Rui Qi; Chao He; Mingmei Yang; Yuanyuan Cai; Guohui Chai (Ecological Economics, 2026)

Environment-responsive multi-enzymed Cu/Cu2O@NC nanorhombic nanoplatform for infected wound antimicrobial treatment - Ji Cheng; Hao Zhang; Yueting Jiang; Zuojia guo; Rui Liu; Xiantao Lin; Hanjin Lu; Yunjun zhang; Wenxuan Fan; Ding Luo; Jinghua Li (Chemical Engineering Journal, 2026)

Mesoporous carbon nanospheres-confined ZnMn2O4/Mn3O4 heterostructures for sustainable zinc-ion storage - Ling-Xin Kong; Songtao Zhang; Yaxun Hu; Peng Liu; Wanchang Feng; Zefan Sang; Xiaotian Guo; Hao Gong; Rui Wang; Dae Joon Kang; Huan Pang (Chemical Engineering Journal, 2026)

Tick-type Schottky contact engineering via Ni-CoOx interlayer for enhanced electron transfer in PEM water electrolyzers - Weiding Wang; Kaini Zhang; Hao Wang; Rui Zhao; Chuanjie Lin; Luning Li; Xinzhe Li; Jinzhan Su; Liejin Guo (Chemical Engineering Journal, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

An energy-spectrum-biased auto-importance sampling method for variance reduction in Monte Carlo energy spectrum simulations - Yang Zhou; Hui Zhang; Zhen Wu; Yisheng Hao; Rui Qiu; Jiajun Wu; Jiahe Shang; Junli Li (Annals of Nuclear Energy, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Hierarchical regulation and molecular functions of co-transcriptional splicing - Rui Niu; Aiming Zhang; Michael G. Rosenfeld; Xiang-Dong Fu; Yajing Hao (Science Bulletin, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Long-term variations and formation drivers of PM2.5 nitrate in a megacity of Guanzhong Plain, China: Implications for air quality management - Liang Wen; Yan Yang; Yujie Zhang; Jiaying Feng; Rui Gao; Wei Guo; Shengnan Guo; Hao Wang; Fahe Chai; Hartmut Herrmann; Andreas Tilgner; Thomas Schaefer; et al. (Journal of Environmental Sciences, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

Vibration-exacerbated suffusion in soils with different gradations: a coupled DEM–PNM study - Si-Rui Chen; Dong-Mei Zhang; Xue-Liang Zhang; Hui-Hao Chen; Zhao-Geng Chen; Xiao-Chuang Xie (Computers and Geotechnics, 2026)

The Matthew effect of defects in microflowers CuS/carbon foam composite optimizes the dielectric response for high-performance microwave absorption - Weibin Deng; Tiehu Li; Arooba Kanwal; Hao Li; Alei Dang; Keke Li; Peng Chang; Rui Zhou; Shengtao Gao; Yating Zhang; Hongjing Wu (Chemical Engineering Journal, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Mitogenome assembly of the floating-leaved aquatic plant Nymphoides peltata provides insights into organellar evolution and aquatic adaptation in Asterales - Rui Dong; Meng-Na Yu; Lei Zhang; Si-Hao Wang; Xi-Ran Tong; Zhi-Zhong Li (Hydrobiologia, 2026)

Acute Stress Drives Adaptive Anxiety via Excitatory-Inhibitory Imbalance in the Prefrontal-Amygdala Circuit in Male Mice - Jia-Xin Zou; En Cao; Zhi-Hao Wang; Rui Han; Xing-Yan Lu; Cheng-Yuan Huang; Xia Qin; Wei-Zhu Liu; Wen-Hua Zhang; Bing-Xing Pan (Neuroscience Bulletin, 2026)

Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

Diameter-independent indices for TBM rock-mass classification - Xiu-xiu Cao; Xu Li; Li-jie Du; Yu-zhi Zhang; Hao Cai; Yun-pei Zhang; Rui-lang Cao (Tunnelling and Underground Space Technology, 2026)

Flexotronic effect-triggered channel switching for high-sensitivity mechanical sensing - Jinwan Chen; Qing Zhao; Zhuangzhuang Zhang; Rui Ge; Hao Sun; Yongkang Zhang; Runze Yu; Longfei Wang; Shuhai Liu (Science Bulletin, 2026)

Revealing the rotational growth of carbon nanotubes by atmospheric environmental transmission electron microscopy - Rui-Hong Xie; Hao An; Lili Zhang; Zichu Zhang; Mengke Zou; Yinghui Pu; Bingsen Zhang; Feng Ding; Chang Liu (Science Bulletin, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Lagged crop responses to drought across China: contrasting multivariate environmental pathways in rainfed and irrigated systems - Rui Yang; Litao Zhou; Hao Yuan; Xinyi Han; Jianhang Zhang; Jiayu Bao; Pengzhou Chen; Shichen Gao; Jianjun Wu (Journal of Environmental Management, 2026)

A tropical fermented-food-derived Lactiplantibacillus plantarum SP055 alleviates DSS-induced colitis through coordinated regulation of gut microbiota and intestinal barrier function - Jianwei Zang; Yibo Shi; Xiaotong Hao; Xia Fan; Yimeng Kou; Wanxiang Zhang; Luyao Xiao; Chang Xu; Tao Lin; Xin Rui; Dan Gan; Wei Li (Food Bioscience, 2026)

Economic rhythms and green tides: Charting China's dual dividends through synergistic policies - Yu-Jie Hu; Rui Zhang; Ailing Luo; Yu Hao (Environmental Impact Assessment Review, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Modeling hiking speed via interpretable machine learning: Uncovering nonlinear impacts of multidimensional environmental factors - Hao Huang; Jin Yeu Tsou; Hao Zheng; Rui Ma; Haochen Shi; Botao Zhang (Applied Geography, 2026)

P2Y12-AMPKα2 signaling contributes to cardiomyocyte senescence in doxorubicin-induced heart failure - Qianqian Niu; Huidan Wang; Mengyao Zhao; Hongdou Zhang; Rui Hao; Peiyao Liu; Lijuan Guo; Bulei Chen; Yuting Xi; Peng Li; Yaling Yin (Molecular and Cellular Biochemistry, 2026)

Correction to: Puerarin alleviates myocardial ischemia-reperfusion injury by enhancing FUNDC1-mediated mitophagy - Na Feng; Anhua Zhang; Lingling Yao; Jie Tang; Min Lu; Dandan Shi; Zhuoran Zhu; Rui Liu; Jun Chen; Xinwen Min; Handong Yang; Hao Xu; et al. (Molecular and Cellular Biochemistry, 2026)

A new seco -norlignan and a rare ring B aromatic 1(10→6) abeo -ergostane-type steroid from Tarlmounia elliptica - Qiao-Long Hao; Han-Mei Bai; Lei Miao; Shuang Yao; Chuan-Rui Zhang (Natural Product Research, 2026)

From addition to regulation: Lactic acid bacteria-driven interfacial mechanisms and spatial control in food bioactive packaging - Jianwei Zang; Yan Luo; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Luyao Xiao; Xin Rui; et al. (Trends in Food Science & Technology, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Duplex real-time qPCR assay targeting β-tubulin SNPs for detection of albendazole resistance in Haemonchus contortus - Xindi Chen; Lili Zhang; Tengyu Wang; Hao Zhang; Rui Wang; Jing Lu; Wa Gao; Wenlong Wang; Chunxia Liu (The Veterinary Journal, 2026)

A long-afterglow-driven all-weather photocatalyst with indirect Z-scheme/Schottky heterojunction for marine antifouling and environmental disinfection - Qi’an Chen; Zhanping Zhang; Yuhong Qi; Miaomiao Ma; Xiwen Guan; Xufeng Zhang; Shukun Zhang; Jingyu Xu; Chuanjun Gu; Sinan Hao; Rui Zhang (Journal of Environmental Chemical Engineering, 2026)

A Ca-MOF@COF composite and its in situ grown gel membrane for highly efficient capture of Cd2+ - Xue-Mei Liu; Chuang-Chuang Zhang; Kun Yang; Wei-Liang Jin; Guan-Lian Mo; Rui Liu; Hong-Xin Jiang; Hao-Jie Cui; De-Ming Kong (Journal of Cleaner Production, 2026)

Genome-wide association study of wheat (Triticum aestivum L.) starch pasting properties - Jiahui Jiang; Hao Chang; Yongji Ma; Rui Jin; Rui Yu; Zhenhua Lu; Tianqi Bai; Yufeng Xu; Ruili Gou; Chengyu Lian; Wenting Zhang; Yingang Hu; et al. (Journal of Cereal Science, 2026)

Accessory minerals constrain anatexis and melt extraction in deep crust and implications for granite genesis - Wenxiang Zhang; Yujie Zhao; Bin Fu; Guangyan Zhou; Hao Wang; Rui Li; Zhaochu Hu; Yuanbao Wu (Geochimica et Cosmochimica Acta, 2026)

Influence of Pt-Cu synergistic action and TiO2 core–shell structure on NH3-SCO and anti-aging performance - Zhenhua Ji; Zhongqiang Bao; Zihao Wu; Peng Zhang; Rui Yang; Ding Luo; Hao Chen (Fuel, 2026)

Gallic acid-modified starch conjugates inhibit harmful aldehydes in fried battered fish: Based on structural characterization and antioxidant activity - Ying Li; Hao Zhang; Jiamu Kang; Meng Yang; Hanyu Liu; Wuyun Chen; Tingting Zhang; Deming Quan; Rui Zhang; Yuan Xia; Xin Du; Xiufang Xia (Food Research International, 2026)

Hydrophobization engineering in nitrile hydratase-nicotinamidase cascade system: Promoting multi-tunnel formation for enhanced niacin biosynthesis - Yinbiao Xu; Rui Wang; Chaofan Li; Yu Liu; Xinyue Zhang; Hao Fu; Zongda Chen; Pei Zhou; Yang Sun; Hua Li; Yupeng Liu (Chemical Engineering Journal, 2026)

Antimony precipitation processes of orogenic and magmatic-hydrothermal gold‑antimony systems in the West Qinling Orogen, China - Lian Zhang; Hao-Cheng Yu; Jie Wang; Rui Zhu; Lei Wang; Deng-Yang He; Jin-Hong Qiu; Jia-Hui Zhou; Kun-Feng Qiu (Chemical Geology, 2026)

Puerarin alleviates myocardial ischemia-reperfusion injury by enhancing FUNDC1-mediated mitophagy - Na Feng; Anhua Zhang; Lingling Yao; Jie Tang; Min Lu; Dandan Shi; Zhuoran Zhu; Rui Liu; Jun Chen; Xinwen Min; Handong Yang; Hao Xu; et al. (Molecular and Cellular Biochemistry, 2026)

Typology-based spatial modeling of urban block commercial vitality: Evidence from Shenzhen for land use planning - Chendi Yang; Hao Huang; Sian Meng; Yunjie Zhang; Jacqueline T.Y. Lo; Rui Ma (Land Use Policy, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Microbiota-responsive BmMBF2-11 limits dysbiosis and promotes intestinal immune homeostasis in the silkworm - Qingxiu He; Rui Yang; Huawei Liu; Huanan Zhu; Yu Zhang; Hao Chen; Qingsong Liu; Guangcheng Huang; Qingyou Xia; Ping Zhao (Insect Biochemistry and Molecular Biology, 2026)

Fish oil emulsion stabilized by multi-modified β-Lg improves lipid metabolism, inflammation, and hepatic–gut homeostasis in high-fat diet mice - Qingchun Zhang; Hao Zhu; Rui Wang; Weilin Liu; Jianfei He; Wei Tang; Jianhua Liu (Food Bioscience, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Fluoride-ion mediated radical scavenging in a hydrophobic microenvironment for durable PEM fuel cells - Xuelin Wei; Gang Zhu; Donghao Ye; Aojie Zhang; Hao Zhang; Wangkai Zhu; Tian Tian; Shengqiu Zhao; Jiangping Song; Rui Chen; Haolin Tang (Chemical Engineering Journal, 2026)

Biotransport and biotransformation of arsenic in earthworm tissues: Advancing vermiremediation strategies of soil contamination - Yunxiang Xu; Muyuan Wang; Yizhao Wu; Yifan Zhang; Rui Jiang; Qi Zhao; Jibao Jiang; Hao Qiu; Yinsheng Li (Chemical Engineering Journal, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Data-driven assessment of nitrogen and phosphorus buffering capacity across 460 Chinese watersheds: Spatial patterns, drivers, and future projections - Yunfei Cao; He Yao; Chuang Zhang; Chaojun Gu; Lin Yang; Rui Hao; Xiao Li; Zhen Wang; Haibing Xiao; Jian Wang; Zhihua Shi (Water Research, 2026)

WaveCastNet-C: Forecasting the significant wave height in the China Sea with a fully convolutional neural network - Hao Dai; Zhihan Xie; Famei Lei; Xining Zhang; Guomei Wei; Rui Lin; Weijie Zhang; Shaoping Shang (Ocean Engineering, 2026)

Integrating distributed hydrologic simulation with low-flow resilience: a spatiotemporal perspective - Yan Zhou; Chi Zhang; Rui Hao; Yongxin Liao; Wei Yin; Dianchang Wang (Journal of Hydrology, 2026)

Evolution of groundwater nitrate during managed aquifer recharge: Insights from DOM characteristics and stable isotopes - Congchao Xu; Rui Li; Weiwu Hu; Liting Hao; Bowen Shi; Tianyu Zhang; Chuanping Feng; Nan Chen (Journal of Hazardous Materials, 2026)

Human Umbilical Cord-Derived Mesenchymal Stem Cells-Involved Strategies: Advancing Tendon Injuries Therapy Towards Clinical Translation - Mumin Cao; Mengze Tong; Yunmeng Pu; Xuepeng Lv; Yimin Sun; Haoyu Zhang; Renwang Sheng; Hao Wang; Yucheng Gao; Guangchun Dai; Fei Xiong; Qianqian Wang; et al. (Stem Cell Reviews and Reports, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Advancement and field evaluation of a honeysuckle harvesting robot with integrated clamping and air-suction mechanisms - Zhaoyu Rui; Zhao Zhang; Cunming Hao; Yingxin Jia; Zhenhuan Ye; Saddam Hussain; Mahmoud A. Abdelhamid; C. Igathinathane; Yiannis Ampatzidis (Computers and Electronics in Agriculture, 2026)

Assessment of genetic diversity and pathogenicity of porcine rotavirus A, and immunogenicity of a bivalent inactivated vaccine in southern China - Guangli Hu; Zhiqing Zhao; Liguo Gao; Rui Geng; Shengjin Liu; Hao Zhang; Yongchang Cao; Hanqin Shen; Chunyi Xue (Veterinary Microbiology, 2026)

From resistance to detection: The role of nanomaterials in plant stress responses - Jing-wan Zhang; Rui-Rui Hao; Abolghassem Emamverdian; Wen-Xun Su; Xing-Hao Zhang; Meisam Zargar; Mo-Xian Chen; Fu-Yuan Zhu (Plant Science, 2026)

Comprehensive analysis of Clade A PP2C family in poplar unveils PtrPP2C-9 as a negative regulator of osmotic stress tolerance through ABF3/GBF3 network - Yuan Zhang; Rui-Quan Wang; Xin-Yi Wang; Shu-Ying Wei; Hao Li; Shuang-Lian Deng; Jia-Hui Liu; Ting Wang; Liang-Hua Chen; Fang He (Plant Science, 2026)

Effects of mung bean addition on quality and starch anti-digestion mechanism of oat noodles - Rui-xian Shang; Wei-feng Zhang; Zi-hao Tu; Xiu-juan Ren; Yan-xia An; Gui-Hong Yin; Jian Zhang; Yang Zhao (Journal of Cereal Science, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Construction and textural modification of soft surimi gel from spanish mackerel (Scomberomorus niphonius) by polysaccharides - Yin-Yin Lv; Xian-Hao Zhang; Jia-Ni Zhou; Ying-Rui Wang; Zhu-Jun Zhang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Longitudinal triglyceride-glucose index and Metal Interactions: A multi-model cohort integrating synergistic and antagonistic indices - Jinhao Jia; Yihong Di; Limeng Xiong; Buyun Liu; Zeyang Bai; Jiaming Fu; Yuhan Zhang; Xiaozhe Geng; Yuxi Wang; Chunqing Gao; Guojie Qiao; Hao Hu; et al. (Environmental Pollution, 2026)

Magnetorheological intelligent chiral metamaterials with ultra-low frequency bandgap - Kaixiang Wang; Jian Zhu; Rui Zhang; Wei Ding; Hao Liu; Tianning Chen (Engineering Structures, 2026)

Interfacial charge threshold induced high-safety energetic co-particles - Hao-Rui Zhang; Yingqi Mao; Minghui Dai; Djalal Trache; Xu Zhao; Zhijian Yang; Qi-Long Yan (Chemical Engineering Journal, 2026)

How biodegradable mulching alters soil nitrogen transformations to enhance soil nitrogen supply and influence gas emissions in a maize cropping system - Hao Zhang; Kai Wang; Jinbo Zhang; Christoph Müller; Dianyuan Ding; Qiang Li; Hengliang Tang; Rui Jiang (Plant and Soil, 2026)

Is China's energy transition pace driven by the supply-side or the demand-side? - Hu Wang; Feng Wang; Juan Liu; Rui Ling; Hao Zhang; Hongfei Jiang (Utilities Policy, 2026)

Suffusion in shield tunnel surrounding soils under train vibration using an improved DEM-PNM coupling method - Si-Rui Chen; Dong-Mei Zhang; Xiao-Chuang Xie; Zhao-Geng Chen; Hui-Hao Chen; Hai-Yun Li (Tunnelling and Underground Space Technology, 2026)

QuaFT: Quality-guided semantic fault intelligence under corrupted industrial data - Lu Ning; Rui Wang; Xiaoran Wei; Hao Huang; Zonghan Zhang; Zehua Chen; Xiaolu Liu; Bo Zhang; Yao Liu; Hao Gong; Kai Song (Process Safety and Environmental Protection, 2026)

Ginkgonins A and B: Two new sesquiterpenoids from Streptomyces ginkgonis TH01 - Yun-Fei He; Jing Miao; Chao Jian; Rui-Jun Wang; Yong-Sheng Gao; Jie-Hao Jin; Xiao-Yi Chen; Ji-Dong Wang; Shao-Yong Zhang (Phytochemistry Letters, 2026)

Multichannel charge separation induced by multiple internal electric fields in ReS2/CoSx/CdS hollow nanostructures for efficient photocatalysis - Qi-Rui Zhang; Yu-Long Wang; Zhi-Hao Deng; You-Long Chen; Si-Jing Ding; Liang Ma (Journal of Environmental Chemical Engineering, 2026)

The enhanced role of formic acid on sulfuric acid-ammonia-driven nucleation in forest regions and polluted city areas - Shasha Chen; Rongrong Li; Chengyan Zhang; Shuqin Wei; Rui Wang; Biwu Chu; Xiaomeng Zhang; Hao Li; Tianlei Zhang (Journal of Environmental Sciences, 2026)

The botryoidal dolomite of the Ediacaran Dengying Formation (Yangtze Craton): Multi-proxy constraints on the terminal Neoproterozoic “dolomite sea” - Yao Wang; Wenlong Ding; Ziyou Zhang; Shuaiyu Shi; Rui Xia; Mengyang Zhang; Hao Jian (Journal of Asian Earth Sciences, 2026)

Transcription factor Schlank positively regulates odorant-binding protein 9 expression to mediate recognition of two volatiles in Nilaparvata lugens (Stål) - Rui-Lin Zhang; Hao-Wei Wang; Man-Qun Wang (Insect Biochemistry and Molecular Biology, 2026)

Grain-size controls on quartz OSL sensitivity in fluvial systems: insights from transport mechanisms in the upper Yellow River - Ya Liu; Song-Xi Du; Jia-Fu Zhang; Xue Rui; Yu-He Shen; Jia-Jing Wang; Qing-Hao Ma; Zheng-Hao Gu (Geomorphology, 2026)

Strain-dependent immunomodulatory activities of lipoteichoic acids from probiotics: From interspecies to intraspecies variation - Yini Liu; Rui Xiao; Min Guo; Jingyu Lu; Jianxin Zhao; Ruojie Zhang; Hao Zhang; Gang Wang; Zipei Zhang (Food Bioscience, 2026)

Quantifying the impact of vegetation greenness change on surface urban heat islands across 133 major cities of China - Rui Yao; Zhihao Zhang; Wenjie Li; Hao Li; Shiya Zhu; Hongji Zhu; Chuan Wang; Dewei Luo; Ying Yang; Junli Li; Weitao Han; Xin Huang (Environmental Research, 2026)

Heterogeneous typing of physical-mental symptoms in stroke patients during recovery phase based on latent class analysis and influencing factors - Li Cao; Rui Song; Bingying Zhai; Zihan Zhang; Xiao Zhang; Yuying Hao (Neurophysiology, 2026)

Eucommia ulmoides leaf extract enhanced growth, supported liver and intestinal function, modulated gut microbiota composition, and increased disease resistance in juvenile largemouth bass (Micropterus salmoides) - Qiang Hao; Tsegay Teame; Rui Xia; Qianwen Ding; Yuanyuan Yao; Chao Ran; Yalin Yang; Zhen Zhang; Zhigang Zhou (Aquaculture, 2026)

Non-degenerate and degenerate soliton solutions to the semi-discrete vector nonlinear Schrödinger system - Yang-Yang Du; Yan-Nan Zhao; Hui-Qin Hao; Rui Guo; Jian-Wen Zhang (Wave Motion, 2026)

GABPα2β2 tetramer deficiency impairs natural killer cell maturation, compromising cytotoxicity and resistance against melanoma - Weiwei Jia; Wanting Zhong; Shanshan Hao; Zhao Wang; Shuaishuai Niu; Yingdi Xu; Yajiao Zhang; Mingxia Feng; Haitao Jiang; Jiarui Zhang; Danli Song; Peiyao Yan; et al. (Science Bulletin, 2026)

Intraspecific competition can stabilize asymmetric nursery pollination mutualisms - Jian-Zhong Gao; Feng Zhang; Derek W. Dunn; Hao Wang; K.Charlotte Jandér; Rui-Wu Wang (Journal of Theoretical Biology, 2026)

TensorSymmetry: a package to get symmetry-adapted tensors disentangling spin-orbit coupling effect and establishing analytical relationship with magnetic order - Rui-Chun Xiao; Yuanjun Jin; Zhi-Fan Zhang; Zi-Hao Feng; Ding-Fu Shao; Mingliang Tian (Computer Physics Communications, 2026)

Soil respiration and its temperature sensitivity on croplands in response to biotic and abiotic factors under straw and nitrogen fertilizer management - Ru Guo; Ruixuan Hao; Xiaoyi Yang; Rui Qian; Zijun Ma; Yunyun Yang; Peng Zhang; Zhikuan Jia; Yuncheng Liao; Xiaolong Ren; Xiaoli Chen (CATENA, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

A dual-mode colorimetric and electrochemical strategy for sensitive detection of PRRSV using imidazole-copper nanozymes - Jing Li; Xiang Lai; Chong Zhang; Yu-Fan Huang; Guo-Bao Ning; Si-Ying Ma; Ao-Xiang Chen; Ming-Rui Li; Guo-Hao Li; Qin Zhao; Can-Peng Li; Hui Zhao (Analytica Chimica Acta, 2026)

Environmental relevant concentrations of TBBPA cause complex toxicological mechanisms - Yuxing Liao; Yilin Wang; Hao Dong; YaJie Lin; Yuxi Xiao; Rummana Jaman; Mohith Mohan; Farheen Azim; Rui Lu; Tengji Zhao; Jiao Zhu; Guiyuan Chen; et al. (Toxicology Letters, 2025)

Reconstructing hydrocarbon accumulation and burial history of Permian reservoirs in northwest Sichuan Basin, China: Integrated fluid inclusion thermometry and U-Pb dating - Rui Ni; Yong Chen; Yifan Song; Hui Zhang; Yanwei Feng; Fang Hao; Xuesong Lu; Xingzhi Ma (Marine and Petroleum Geology, 2025)

The Eocene blueschist in Zeyarat metamorphic complex, Iranian Makran: Implication for subduction dynamics in plates interface - Zhou Tan; Wenjiao Xiao; Rasoul Esmaeili; Parisa Gharibnejad; Miao Sang; Qigui Mao; Hao Wang; Rui Li; Zhiyong Zhang; Jien Zhang (Lithos, 2025)

Precise construction of Anderson-type polyoxometalate-based covalent organic frameworks for photocatalytic hydrogen peroxide production - Zhang-Di Liu; Zai-Xiang Zhang; Yang Yang; Rui Xing; Zi-Hao Wei; Hou-He Liu; Jiang-Bo Ming; Jin Zhu; De-Yin Wang (Journal of Water Process Engineering, 2025)

Synergistic KOH/MgSO₄ activation of hazelnut shell biochar: Tailored hierarchical porosity and surface chemistry boosting high-efficiency capacitive deionization - Shumin He; Youzhao Wang; Xiaolong Gao; Jiedong Hao; Enbo Zhang; Rui Du; Tengfei Li; Yaonan Zhu; Tong Zhu (Journal of Environmental Chemical Engineering, 2025)

Location-specific climate and environmental benefits of China’s coal mining phase-down towards carbon neutrality - Hao Li; Tao Yang; Linman Li; Bin Lu; Tianzheng Zhang; Xiaolong Lu; Rui Peng; Zhaohua Wang (Global Environmental Change, 2025)

Multi-modified β-Lg-stabilized fish oil emulsions: physicochemical stability, antioxidant capacity, and bioavailability in Caco-2 cells - Qingchun Zhang; Hao Zhu; Rui Wang; Jianfei He; Christos Ritzoulis; Owen Griffith Jones; Weilin Liu; Wei Tang; Jianhua Liu (Food Chemistry, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Superacid polymer electrolyte with end-group-protected proton sites mitigates ammonia poisoning for efficient electrochemical hydrogen separation from ammonia cracking reformate gas - Jiaqi Shuai; Hao Li; Zhengrui Xiao; Zeqi You; Yucong Liao; Rui Wang; Yafeng Li; Yuanwei Yan; Jiangping Song; Tian Tian; Lan Zhang; Siew Hwa Chan; et al. (Chemical Engineering Journal, 2025)

Different Chemical Fertilization Levels Affect Arbuscular Mycorrhizal Fungal Communities in Rhizosphere Soils of Ratoon Sugarcane - Xiao-Juan Qin; Sheng Wang; Ying-Jie Nong; Yi-Hao Kang; Jin-Lian Zhang; Shi-Yuan Zeng; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2025)

Quantifying the relative importance of factors influencing rainfall partitioning in a rainfed apple orchard - Rui Zhang; Li Wang; Hao Liu (Hydrological Sciences Journal, 2025)

Multiscale responses of gap-graded soil under the combined effect of train vibration and seepage erosion - Dong-Mei Zhang; Hui-Hao Chen; Xiao-Chuang Xie; Si-Rui Chen; Zhao-Geng Chen; Jia-Ping Li (Transportation Geotechnics, 2025)

Post-collisional crustal evolution in the central Lhasa block of southern Tibet: Insights from early and late Cretaceous magmatism - Shu-Ya Huang; Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Wan-Long Hu; Qing-Qing Mo; Mao-Rui Liu; Yue Qi; Wei Dan; Xiu-Zheng Zhang (Lithos, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

Enhanced electrocatalytic oxidation of high-salinity quaternary ammonium compound wastewater using CNTs-(Ru Ir O2)/Ti Anode - Hao-Tian Liu; Han-Qing Zhao; Yi-Rui Yang; Shuang Wu; Jia-Ping Huang; Rui-Han Yu; Hongcheng Bai; Aqiang Ding; Daijun Zhang; Peili Lu (Journal of Environmental Sciences, 2025)

Effect of egg white peptides‑selenium chelate against APAP-induced damage in HepG2 cells and C. elegans via Nrf2 signaling - Yuwei Wu; Yiqiao Pei; Wenjie Wang; Siyu Du; Fengshi Shang; Zhifu Liu; Rui Liu; Ye Zhang; Hao Wang (Food Chemistry, 2025)

Hierarchical Janus sponge evaporator functionalized with liquid-like PDMS molecular brushes for efficient and sustainable solar evaporation and electricity generation - Siying Guan; Taolin Zhang; Shouzheng Jiao; Rongxue Xi; Rui Ma; Chenshun Hu; Yuwei Hao; Zhicheng Sun; Zhongjun Cheng (Chemical Engineering Journal, 2025)

Optimizing electromagnetic attenuation properties via controlled dielectric polarization in Zn single-atom-decorated polymer-derived SiZnCN ceramics - Hao Deng; Yang Li; Ruihua Chen; Chao Ma; Junpeng Jiang; Daoyang Han; Bingbing Fan; Hailong Wang; Rui Zhang; Gang Shao (Chemical Engineering Journal, 2025)

Ni/Al2O3 catalysts for the selective hydrogenation of 1,3–butadiene to butene: From theoretical research to experimental proving - Linxia Cui; Mingyuan Zhang; Xin Chen; Yuanyao Xie; Yang Jiang; Rui Gao; Haigang Hao (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Electrospun Mn-doped ZIF-67 composite nanofibers with high water stability for efficient adsorption of antibiotics in aqueous systems - Xiaolin Yue; Can Cui; Shaolin Deng; Lan Wang; Ping Li; Anhong Li; Yizhong Zhang; Rui Hao; Wenyuan Tan (Journal of Environmental Chemical Engineering, 2025)

Synergistic engineering of four-pointed star-like layered stacking and oxygen vacancies toward high-efficiency Bi2O2-xSe photocatalysts for the degradation of tetracycline and Congo red - Yao Yang Liu; Zhong Li; Yi Liang; Jing Hao Zhuang; Wen Ji Zhang; Tao Tang; Yin Fen Cheng; Rui Ou; Bao Yue Zhang; Jian Zhen Ou (Journal of Environmental Chemical Engineering, 2025)

Utilizing a three-zone control model of adaptive concentrating photovoltaic facade to enhance visual comfort and energy benefits - Bo Wang; Yifan Xu; Hao Wang; Xinshuo Zhang; Yuan Chen; Rui Tang; Ayin Yan; Mengli Zhang; Ying He (Energy and Buildings, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

Jugular Vein Evans Blue Injection for Blood–Brain Barrier Assessment Following Hemorrhagic Stroke in a Mouse Model - Yu Zeng; Fang Wang; Rui Liu; Jian liu; Tao Xiong; Guodong Liu; Hao Yin; Guoqiang Han; Jian liu; Jiqin Zhang; Ying Tan (Translational Stroke Research, 2025)

A novel method for predicting debris flow hazard: a multi-strategy fusion approach based on the light gradient boosting machine framework - Tianlong Wang; Qi Ge; Tianxing Ma; Hao Chen; Rui Luo; Xu Wang; Keying Zhang; Zhaowei Chu; Xiaohui Ni; Hongyue Sun (Stochastic Environmental Research and Risk Assessment, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Flavonoids as Signals Mediate Plant-nematode Communication Through Regulating Nematode Perceptual Ability - Xiang-Yu Zhang; Rui Yuan; Yaseen Ullah; Xu-Dong Li; Hao-Ran Li; Wei Zhang (Journal of Chemical Ecology, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Unsupervised domain adaptation semantic segmentation method for wheat disease detection based on UAV multispectral images - Yuchen Zhang; Xingan Hao; Feilong Li; Zexi Wang; Dongxiang Li; Mei Li; Rui Mao (Computers and Electronics in Agriculture, 2025)

Development and field evaluation of a straddle-frame honeysuckle harvesting robot - Zhaoyu Rui; Zhao Zhang; Cunming Hao; C. Igathinathane; Afshin Azizi; Xiaofei Wu; Man Zhang; Fazeel Abid; Seyed Mohamad Javidan (Biosystems Engineering, 2025)

New point mutations in osmosensing two-component histidine kinase gene associated with iprodione resistance in Monilinia fructicola field isolates from China - Qian Long; Yiyi Guo; Miaomiao Yi; Changsheng Lu; Rui Zhong; Hao Zhang; Usama Amin; Dufang Ke; Zongwen Wang; Fengping Chen (Pesticide Biochemistry and Physiology, 2025)

Electrocatalytic removal of nitrate by non-noble Fe3C/Cu: Property, mechanism, and practical water treatment performance - Yang Guo; Hao Chen; Houfen Li; Jiming Liu; Xiao Zhang; Aijuan Zhou; Xiuping Yue; Rui Li; Jindong Wang; Pengxiao Liu; Hongtao Yu; Xu Zhao (Journal of Hazardous Materials, 2025)

Computer-aided precise hapten design strategy for the monospecific detection of altrenogest: Experimental validation and analysis of the molecular recognition mechanism - Hongfei Yang; Hao Wen; Yu Si; Mingyue Ding; Yiting Liu; Ziyan Yu; Linwei Zhang; Jiacan Wang; Xiaoming Pan; Shiyun Han; Yiting Wang; Shixiang Wu; et al. (Food Chemistry, 2025)

Protective effects of rosmarinic acid against oxidative damage and atherosclerosis via the PI3K/AKT pathway - Tiantian Tang; Mingze Sun; Baiyuan Sha; Rui Liu; Zhiyang Ren; Liwei Li; Ye Zhang; Hao Wang; Kai Yu (Food and Chemical Toxicology, 2025)

Holographic, traceable, and switchable anti-counterfeiting using temperature-tolerant relief gratings on polyimide substrate - Chengwei Xiao; Haixian Shi; Hao Zhong; Chengbin Zou; Yiyong Chen; Jinru Li; Weien Liang; Wanying Zhang; Dezhi Zhan; Shilong Zhong; Rui Chen; Zhaoxiang Zhu; et al. (Chemical Engineering Journal, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

SiO2-assisted co-assembly of ultrafine aramid nanofiber-based porous thermal-resistant separator for Lithium-ion batteries - Fuhai Guo; Minghan Xu; Shi Feng; Keyu Zhang; Xiaotong Zheng; Hao Xue; Fulan Hao; Rui Zhuang; Qingchun Liu; Lei Zhang; Jianjun Zhang; Qingfu Wang (Chemical Engineering Journal, 2025)

Kinematic mechanisms of coordinated fore and hind hoof movements for stability enhancement and energy efficiency in reindeer long-distance migration - Kaixiang Chen; Rui Zhang; Wenchao Dong; Hao Pang; Guoyu Li; Lige Wen (Polar Biology, 2025)

Xylem hydraulic impairment due to stronger drought stress accounts for the reduced crown vitality and growth performance of Mongolian pine trees in higher-density plantations - Xue-Wei Gong; Yi-Lei Ouyang; Yan-Yan Liu; Jin-En Zhang; Zhao-Kui Li; Hong-Li Li; Zhuo-Qun Fang; Yu Cao; De-Dong Wu; Qiu-Rui Ning; Guang-You Hao (Agricultural and Forest Meteorology, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Exploring the psychological impacts of air contamination: A cross-national study - Yu Hao; Shiyao Liu; Xueyu Rui; Xiaoxiao Hu; Lu Wang; Shen Wang; Guisen Zhang; Asyraf Afthanorhan; Zhi-Nan Lu (Journal of Environmental Management, 2025)

3D inversion of airborne transient electromagnetic data using deep learning - Shuowei Zhang; Rui Liu; Hao Feng; Zhihong Wang; Shangbin Liu; Yan Luo; Ziqiang Zheng; Huaifeng Sun (Journal of Applied Geophysics, 2025)

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Drivers of ecosystem service trade-off changes in different climate zones: a case study of the Sichuan–Yunnan–Loess plateau ecological shelter, China - Hao-Rui Li; Shuai Ma; Ming Zhang; Yun-Ke Yin; Hai-Bo Hu; Liang-Jie Wang; Jiang Jiang (Environment, Development and Sustainability, 2025)

Streptococcus suis AdcA interacts with factor H and inhibits C3b deposition on the bacteria to participate in complement evasion - Siqi Pang; Zhulin Qiao; Jiajia Xu; Hao Tang; Qiuhong Zhang; Weiyao Han; Lu Peng; Jiaojiao Yang; Jiao Zhang; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Aluminum and microplastic release from reflective agricultural films disrupt microbial communities and functions in soil - Kai Wang; Markus Flury; Yakov Kuzyakov; Hao Zhang; Wei Zhu; Rui Jiang (Journal of Hazardous Materials, 2025)

Synthesis of high yield mesoporous silica for efficient CO2 adsorption using coal gasification fine slag - Zekai Miao; Hao Ge; Xinran Han; Rui Wu; Hai Zhu; Congchao Zhang; Shengping Wang (Fuel, 2025)

Flexural behavior of reinforced concrete beams subjected to natural corrosion in marine environment - Yang Liu; Wei-Ping Zhang; Chao Jiang; Feng Wu; Jun-Li Qiu; Rui-Lin Wang; Nai-Hao Zheng (Engineering Structures, 2025)

Transcriptomics and Metabolomics Analysis Reveal the Mechanism of Hormones Regulation of the Flower Bud Formation and Development in Phalaenopsis Orchid - Xiaofen Gao; Yang Hao; Xiaoying Yang; Yanping Shi; Li Zhang; Rui Yan (Journal of Plant Growth Regulation, 2025)

Cerebellar large-scale network connectivity in Parkinson’s disease: associations with emotion, cognition, and aging effects - Chentao He; Zhenzhen Chen; Mengfei Cai; Piao Zhang; Hao Li; Xi Chen; Qi Qi; Rui Yang; Yan Li; Zaiyi Liu; Lijuan Wang; Yuhu Zhang (Brain Imaging and Behavior, 2025)

Bisphenol S promotes clear cell renal cell carcinoma progression by modulating the WNT5A-dependent EMT pathway - Hua Zhang; Fei Lin; Bo-Han Lin; Xiong-Lin Sun; Qing-Shui Zheng; Rui Gao; Yong Wei; Shao-Hao Chen; Xue-Yi Xue (Toxicology, 2025)

Mangiferin promotes porcine oocyte maturation and delays the postovulatory aging process by up-regulating NRF2 levels - Xiuwen Yuan; Hewei Ji; Yuhao Zhang; Huilin Peng; Neng-hao Cao; Jia-jun Ren; Xue-rui Yao; Xingwei Liang; Nam-hyung Kim; Yong-nan Xu; Ying-hua Li (Theriogenology, 2025)

Nitrogen addition and rhizosphere effects differentially shape prokaryotic and fungal communities in peanut–maize cropping systems - Yang Chen; Zejin Zhang; Yichao Rui; Carson Pearl; Sheng Lu; Fang Wang; Flemming Ekelund; Yanbin Hao; Xiaoyong Cui (Rhizosphere, 2025)

Intelligent double-layer pads containing blueberry anthocyanins/citric acid/tricolor lake for chilled pork real-time freshness monitoring - Junna Sun; Ye Zhang; Rui Liu; Jian Du; Qingdai Liu; Tianxin Wang; Yuan Wang; Hao Wang (Food Chemistry, 2025)

Discovery of novel DPP4 inhibitory peptides from egg yolk by machine learning and molecular docking: In vitro and in vivo validation - Yujie Xu; Yiqiao Pei; Zhifu Liu; Peng Tan; Rui Liu; Lulu Chu; Ye Zhang; Wenjie Wang; Hao Wang (Food Chemistry, 2025)

Blast response and multi-objective optimization of multi-layered kirigami corrugated sandwich panels - Hao Liu; Zengshen Yue; Rui Zhang; Jiawei Lu; Jian Zhu (Engineering Structures, 2025)

Field and numerical investigations on linkage failure of the main roof and pumpable supports in the pre-excavation recovery room - Dong Zhang; Jianbiao Bai; Yonghong Guo; Zizheng Zhang; Rui Wang; Zhijun Tian; Shuai Yan; Qiancheng Zhu; Min Deng; Hao Fu; Shuaigang Liu (Engineering Geology, 2025)

Corrigendum to ‘Design of polypyrrole layer enhanced MIL-88B(Fe) composite electrode material for electrosorption separation of copper ions’ [Desalination 603 (15 May 2025) 118606] - Lujie Nie; Yanna Ren; Lei Wang; Yingying Wang; Jiajun An; Jiajin Hao; Jiaqi Wang; Chen Zhao; Xin Zhang; Yongtao Lv; Miaolu He; Hongyun Nie; et al. (Desalination, 2025)

Multi-shank flexible implantable neural interface for long-term olfactory neuron recording toward odor perception - Qunchen Yuan; Jiale Wang; Chunlian Qin; Shunuo Shang; Haoze Xu; Fan Wu; Yong Qiu; Haoting Zhang; Rui Sun; Ping Wang; Liujing Zhuang; Hao Wan (Chemical Engineering Journal, 2025)

Modeling and Quantitative Assessment of Critical Defects in Shield Tunnels with Cascading Effects - Xiangyu Chang; Rui Zhang; Jianxiao Mao; Yuguang Fu; Hongyun Fan; Hao Wang (Geotechnical and Geological Engineering, 2025)

Mesoscopic interpretation of fines clogging-induced permeability changes in completely decomposed granite - Rui Chen; Zhi-yuan Luo; Ai-guo Li; Hao Wang; Lei-lei Liu; Liang-liang Zhang (Bulletin of Engineering Geology and the Environment, 2025)

The antioxidant protein PntA coordinates with OmpW to resist oxidant stress in Actinobacillus pleuropneumoniae - Weiyao Han; Qiuhong Zhang; Zhen Luo; Hao Tang; Xiabing Chen; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Design of polypyrrole layer enhanced MIL-88B(Fe) composite electrode material for electrosorption separation of copper ions - Lujie Nie; Yanna Ren; Lei Wang; Yingying Wang; Jiajun An; Jiajin Hao; Jiaqi Wang; Chen Zhao; Xin Zhang; Yongtao Lv; Miaolu He; Hongyun Nie; et al. (Desalination, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Cation-induced phase transformation in PVDF for efficient energy harvesting - Dinku Hazarika; Jiaqi Lu; Jiafeng Ni; Chuanrui Chen; Muhammad Naeem Shah; Liangquan Xu; Jianhui Wu; Kaihang Zhang; Jie Li; Xinyu Cai; Rui Wan; Hao Jin; et al. (Chemical Engineering Journal, 2025)

Design optimization of dual-circulation wells using deep learning - Yang Sikai; Fang Zhang; Ma Yanling; Ke Hao; Zhou Rui; Muhammad Sadam (Stochastic Environmental Research and Risk Assessment, 2025)

Metabolomics provide novel insights into the settlement and metamorphosis of the scyphozoan jellyfish Aurelia coerulea - Shuai Liu; Xiaoyu Tang; Xuerui Liu; Rui Zhang; Xiangrui Guo; Zhen Yu; Ye Zhao; Jiehui Yin; Hao Sun; Yanying Zhang (Journal of Oceanology and Limnology, 2025)

Cardiovascular dysfunction and altered lysosomal signaling in a murine model of acid sphingomyelinase deficiency - Yun-Ting Wang; Alexandra K. Moura; Rui Zuo; Kiana Roudbari; Jenny Z. Hu; Saher A. Khan; Zhengchao Wang; Yangping Shentu; Mi Wang; Pin-Lan Li; Jiukuan Hao; Yang Zhang; et al. (Journal of Molecular Medicine, 2025)

Optimizing cultivation substrate moisture and calcium application for the comprehensive growth of cucumber under different air temperatures - Jing Wang; Feng Qu; Jiayue Zhang; Rui Zhao; Hao Wang; Xiaohui Hu (Irrigation Science, 2025)

Applicability analysis of passive containment heat remove system calculation model based on integrated code - Nan Zhang; Shuai Yuan; Xiang Xia; Chang Wang; Rui Hao (Annals of Nuclear Energy, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Atmospheric carbonyls in urban Beijing in the summertime under the continuous implementation of clean air actions: Decreasing trends, source apportionments and new insights for control strategies - Xin Zhang; Fang Bi; Mingzhu Li; Lu Zhao; Hao Zhang; Yunfeng Li; Likun Xue; Rui Gao; Yujie Zhang; Xuezhong Wang; Zhenhai Wu; Zhanshan Wang; et al. (Journal of Cleaner Production, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Correlation of lipid hydrolysis, oxidation, and molecular transformation with volatile compound revolution in pork during postmortem wet-aging process - Kaihua Zhang; Rui Hao; Shouwei Wang; Zheqi Zhang; Dan Li; Xiaoman Li; Bing Zhao; Shunliang Zhang; Yan Zhao; Xiangning Chen (Food Chemistry, 2025)

A large-scale gene co-expression network analysis reveals Glutamate Dehydrogenase 2 (GhGDH2_D03) as a hub regulator of salt and salt-alkali tolerance in cotton - Rui Hao; Zhan Gao; Xianliang Zhang; Xingxing Wang; Wuwei Ye; Xiugui Chen; Xiongfeng Ma; Xianpeng Xiong; Guanjing Hu (Plant Molecular Biology, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Ratio Fluorescence Sensor Based on Bimetal MOFs for the Detection of Hg2+and H2O2 - Bo-Ming Han; Hao-Rui Zhang; Wen-Jie Gao; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Journal of Fluorescence, 2025)

Detecting wheat yellow dwarf disease by employing a Dual-Branch multiscale model from UAV multispectral images - Xingan Hao; Zexi Wang; Yuchen Zhang; Feilong Li; Meili Wang; Jialin Li; Rui Mao (Computers and Electronics in Agriculture, 2025)

Vertical migration characteristics of polychlorinated biphenyls (PCBs) in estuarine and coastal zones under complex environmental conditions - Rui Pan; Nan Zhang; Jiqing Li; Xiao Xiao; Hao Wu; Xianzhang Dang; Shuya Hu (Marine Pollution Bulletin, 2025)

Novel approaches for alleviating shallow soil compaction using microbial fertilizers and their beneficial impacts on plant growth and soil physicochemical properties - Xiang Yao; Hailin Guo; Dandan Li; Junqin Zong; Rui Zhang; Jingbo Chen; Dongli Hao; Xinyong Zhao; Jianxiu Liu; Haoran Wang; Chunjie Li (Soil and Tillage Research, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

Fish oil emulsions stabilized by enzymatic hydrolysis, glycation, and fibrillation of β-Lg: Stability and EPA/DHA bioaccessibility - Qingchun Zhang; Hao Zhu; Rui Wang; Jianfei He; Christos Ritzoulis; Weilin Liu; Wei Tang; Jianhua Liu (Food Chemistry, 2025)

Amelioration of myofibrillar protein emulsion gel properties by mildly oxidized sunflower oil - Jinyang Chang; Rui Liu; BeiBei Zheng; Xinzhu Gao; Baorui Li; Ye Zhang; Tianxin Wang; Hao Wang (Food Chemistry, 2025)

Environmentally relevant concentrations of DBDPE (decabromodiphenyl ethane) induce intestinal toxicity in silkworms (Bombyx mori L.) - Xue Luo; Rui Xing; Man Xu; Hui-Jun Jiang; Yu-Rui Wang; Ming-Yue Hu; Hao Zhang; Feng Ge; Wei Zhang; Hong-Wei Wang (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

Seismic Prediction Methods for Tidal Flat Sand Bodies in the Shunbei Area of the Tarim Basin - Zhi-peng Sun; Rui-zhao Yang; Jing-rui Chen; Hao Zhang; Shi-jie Zhang; Peng-hui Yang; Feng Geng (Applied Geophysics, 2025)

TreegrowNet: a completion network for incomplete single tree point cloud from TLS - Tao Zhang; Chunhua Hu; Jiangang Han; Hao Sun; Rui Wang; Zhen Jing (International Journal of Remote Sensing, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

Erroneous Differentiation of Tendon Stem/Progenitor Cells in the Pathogenesis of Tendinopathy: Current Evidence and Future Perspectives - Yucheng Gao; Hao Wang; Liu Shi; Panpan Lu; Guangchun Dai; Ming Zhang; Bowen Han; Mumin Cao; Yingjuan Li; Yunfeng Rui (Stem Cell Reviews and Reports, 2025)

Spatial Characteristics of the Plasma Spark Source Wavelet - Jia Wei; Xiaozhu Hao; Jing Feng; Rui Yang; Lei Xing; Huaishan Liu; Wei Wang; Zhiqiang Wu; Dong Zhang; Linwei Li (Journal of Ocean University of China, 2025)

Assessment of Peripheral Neuropathy Using Current Perception Threshold Measurement in Patients with Spinocerebellar Ataxia Type 3 - Xia-Hua Liu; Wei Lin; Hao-Ling Xu; Mao-Lin Cui; Zhuo-Ying Huang; Ying Li; Nan-Nan Zhang; Ning Wang; Zhi-Yong Wang; Shi-Rui Gan (The Cerebellum, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

DFT study the influence of active site structure on the electrocatalytic nitrogen reduction reaction - Ke Shi; Linxia Cui; Mingyuan Zhang; Yang Jiang; Rui Gao; Haigang Hao (Fuel, 2025)

Design method of simplified dynamic test model for high-rise building with underground structures considering nonlinear behavior similarity - Rui Wang; Zhi-Qian Dong; Gang Li; Ding-Hao Yu; Yao-Zhong Cui; Han Zhang; Jia-Long Li (Engineering Structures, 2025)

Enhanced wastewater treatment using biochar-supported layered-double-hydroxide composites - Ao Huang; Nan Zhang; Qian-Bin Wang; Bo-Han Zhao; Rui-Bao Zhang; Ming Cheng; Chen Shi; Xiao-Di Hao (Chemical Engineering Journal, 2025)

Readily recyclable, degradable, stretchable, highly conductive, anti-freezing and anti-drying glycerohydrogel for triboelectric nanogenerator - Sihan Jiang; Yang Wang; Meiqin Tian; Haiyang Zhang; Rui Wang; Haokun Yan; Hao Tan; Rasoul Esmaeely Neisiany; Wei Sun; Zhengwei You (Chemical Engineering Journal, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

Eliminating bacterial endotoxins and associated inhalation hazards in reclaimed water via ultraviolet/ferrate combination disinfection - Muhan Sun; Xiaoxu Jiang; Rui Liu; Deqin Kong; Hao Wu; Zhao Wang; Gang Zheng; Chongmiao Zhang; Weihua Yu (Chemical Engineering Journal, 2025)

Therapeutic Potential of Mesenchymal Stem Cell-Derived Exosomes in Spinal Cord Injury - Jing An; Bo Chen; Rui Zhang; Ding Tian; Kuohao Shi; Lingling Zhang; Gaorong Zhang; Jingchao Wang; Hao Yang (Molecular Neurobiology, 2025)

Formation and evolution of thermokarst landslides in the Qinghai-Tibet Plateau, China - Tao Wei; Hao Wang; Peng Cui; Yan Wang; Bo Zhang; Rui-Long Wei; Zhen-Xing Liu; Chao-Yue Li (Science of The Total Environment, 2024)

Mechanisms of selectivity for azadirachtin in honeybees (Apis cerana): A new strategy for avoiding thiamethoxam ingestion - Hao Wu; Sheng-nan Li; Rui-quan Hou; Peng-rui Du; Kun-yu Zhao; Muhammad Zeeshan; Han-hong Xu; Zhi-xiang Zhang; Pei-wen Zhang (Pesticide Biochemistry and Physiology, 2024)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Holocene paleoenvironment of the Nihewan Basin, China, inferred from high-resolution luminescence dating and a multiproxy analysis of gully sediments - Qing-Hao Ma; Yu-Jie Guo; Hua-Rui Lei; Yu-He Shen; Jia-Jing Wang; Ya Liu; Zhen-Yu Zhou; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Physical mechanism-based simulation methods for soil and ground heat flux from observations at multi-sites - Zhaofei Liu; Dong Jiang; Rui Wang; Mengmeng Hao; Xingxing Zhang (Journal of Hydrology, 2024)

Embryonic exposure to glycopeptides induces acute toxicity and developmental neurotoxicity in zebrafish (Danio rerio) - Kehui Liu; Jiyang Du; Yuanyuan Ma; Haicheng Hu; Xinyan Ma; Rui Zhang; Hao Wang; Liyan Yu; Jingpu Zhang; Ying Han (Journal of Hazardous Materials, 2024)

Ultrabright silicon nanoparticles combined with o-phenylenediamine for ratiometric fluorescence and smartphone imaging dual-mode detection of nitrite - Wen-Jie Gao; Ming-Yue Tian; Xing-Hui Ren; Hao-Rui Zhang; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Journal of Hazardous Materials, 2024)

Endogenous phosphorus release from plateau lakes responds significantly to temperature variability over the last 50 years - Chao Yan; Rui Xia; Yan Chen; Lixin Jiao; Xiaoyu Liu; Yingze Yin; Qiang Hu; Kai Zhang; Lina Li; Hao Liu (Journal of Environmental Management, 2024)

Comparative organic pollutants removal efficiency and life cycle assessment of pyrolysis and solvent elution for industrial waste salt recycling - Xinyu Huang; Hao Wang; Min Song; Rui Chen; Saijun Lv; Haoqing Zhang; Chuqi Wang; Jerome Ramirez; Xiuxiu Ruan (Journal of Environmental Management, 2024)

Composition of four polyphenol fractions extracted from partridge tea and their mechanisms on ameliorate insulin resistance in HepG2 cells - Ke-Xin Hao; Ying-Jing Zhang; Rui-Fang Zhong; Yi-Meng Li; Ling Wang; Xiao Chang; Da-Wei Wang; Jian-Guo Jiang; Wei Zhu (Food Bioscience, 2024)

Molecular engineering in thizolo[5,4-d]thiazole-based donor-acceptor covalent organic framework Induced high-efficient photosynthesis of H2O2 - Ding-Ming Xue; Yi-Jun Zhang; Jing-Wen Chen; Hao Yang; Rui-Jie Xie; Shi-Chao Qi; Yuan-Qing Bu; Fei Liu; Hou-Hu Zhang; Jacques Lalevée (Chemical Engineering Journal, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Community of Arbuscular Mycorrhizal Fungi in the Rhizosphere Soils with Different Generations of Hybridized Progeny of Wild Erianthus arundinaceus and Sugarcane - Jin-Lian Zhang; Yi-Hao Kang; Juan Song; Huan-Ying Xu; Wei Zhang; Ying-Jie Nong; Qian Wang; Qin-Nan Wang; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

The effect of green coffee extract supplementation on obesity indices: critical umbrella review of interventional meta-analyses - Zhao Yang; Zhuo Shao; Weiyi Ouyang; Lu Ying; Rui Guo; Mingxuan Hao; Youfeng Liang; Wenjing Zhang; Xiaoyang Chen; Ruolan Chen; Changyuan Yu; Kousalya Prabahar; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Green manuring combined with zeolite reduced nitrous oxide emissions in maize field by targeting microbial nitrogen transformations - Rui Liu; Danna Chang; Guopeng Zhou; Hao Liang; Jiudong Zhang; Qiang Chai; Weidong Cao (Science of The Total Environment, 2024)

Dynamics of impure CO2 and composite oil in mineral nanopores: Implications for shale oil recovery and gas storage performance - Lu Wang; Run Zou; Yifan Yuan; Yifan Zhang; Rui Zou; Liang Huang; Yisheng Liu; Zhan Meng; Hao Chen (Chemical Engineering Journal, 2024)

Delaying cyclization of polyacrylonitrile by boric acid for sulfurized poly(acrylonitrile) cathode materials - Xuan Zhang; Hui-Chao Lu; Chen-Ran Hao; Ji-Qiong Liu; Xi-Rui Kong; Jiu-Lin Wang (Chemical Engineering Journal, 2024)

Perovskite nanocrystals photo-initiated in situ encapsulation for optical tracking - Xiao’e Jia; Tongyu Shi; Qingyuan Zhang; Hao Huang; Paul K. Chu; Xue-Feng Yu; Rui He (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Assessing the role of urban green infrastructure in mitigating summertime Urban Heat Island (UHI) effect in metropolitan Shanghai, China - Hao Zhang; Meng-yuan Kang; Zhen-ru Guan; Rui Zhou; Ai-lian Zhao; Wen-jia Wu; Hao-rong Yang (Sustainable Cities and Society, 2024)

Long-term escape behavior and release mechanism of organic emissions from asphalt materials - Rui Zhang; Naipeng Tang; Hongzhou Zhu; Yuan Xi; Rui Li; Gengren Hao (Science of The Total Environment, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Enhancing soil gross nitrogen transformation through regulation of microbial nitrogen-cycling genes by biodegradable microplastics - Hao Zhang; Wei Zhu; Jinbo Zhang; Christoph Müller; Lifen Wang; Rui Jiang (Journal of Hazardous Materials, 2024)

Migration mechanism of atrazine in the simulated lake icing process at different freezing temperatures based on density function theory - Yan Zhang; Hao Lin; Aixin Yu; Xiaozhuang Wang; Yucan Liu; Tongshuai Liu; Chen Zhao; Rui Mei (Journal of Environmental Sciences, 2024)

Enhanced oxidative stability and quality of chilled mirror carp fillet using an antioxidant film of chitosan/clove essential oil nanoemulsion - Ying Li; Litong Rui; Hao Zhang; Xiufang Xia (Food Bioscience, 2024)

Quantitative evaluation method for post-earthquake functionality loss of pedestrian flow pathways within a complex building using evacuation and rescue simulation - Zhao-Long Shi; Zhi-Qian Dong; Gang Li; Ding-Hao Yu; Han Zhang; Rui Wang (Engineering Structures, 2024)

Computational engine for finite element digital twins of structural dynamics via motion data - Youqi Zhang; Rui Hao; Jarkko Niiranen; Yaohua Yang; Eugen Brühwiler; Di Su; Tomonori Nagayama (Engineering Structures, 2024)

Monitoring crack opening via seismic velocity variation to assess that fatal effect of precipitation for landslide motion - Zhiqiang Liu; Chuntao Liang; Christoph Sens-Schönfelder; Wei Hu; Xinlei Sun; Tuo Zhang; Rui Xu; Zhiyu Jiang; Hao Jiang (Earth and Planetary Science Letters, 2024)

Novel catalytic membrane based on γ-FeOOH@PVDF/peroxymonosulfate for efficient ammonia recovery: Self-cleaning mechanism and emerging organic contaminant degradation performance - Wucheng Ma; Chenfei Liu; Liang Zhu; Rui Han; Wei Zhang; Hao Zhang; Linting Zhao; Shi Wang; Lin Chen; Yiping Li (Chemical Engineering Journal, 2024)

Suppression the glucose-induced ferroptosis in endothelial cells by 4OI-loading exosomes hydrogel for the treatment of diabetic foot ulcer - Kuo Shen; Rui Zheng; Bangrui Yu; Hao Zhang; Peng Wang; Peng Zhao; Jijun Chen; Yixuan Yuan; Yuhang Wang; Kejia Wang; Yanhui Jia; Ruizhi Wang; et al. (Chemical Engineering Journal, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

High-altitude exposure leads to increased modularity of brain functional network with the increased occupation of attention resources in early processing of visual working memory - Jing Zhou; Nian-Nian Wang; Xiao-Yan Huang; Rui Su; Hao Li; Hai-Lin Ma; Ming Liu; De-Long Zhang (Cognitive Neurodynamics, 2024)

A multifunctional barium-modified geopolymer foam for the efficient and flexible treatment of high-sulfate coal mine drainage - Xuhao Zhang; Xiao Zhang; Minghui Ma; Rui Cheng; Chenglong Hao; Li Zhang; Jiaqi Zhang (Chemical Engineering Journal, 2024)

Mutations in wheat TaAPA2 gene result in pleiotropic effects on plant architecture - Shengsheng Bai; Guiping Wang; Rui Song; Yanna Liu; Lei Hua; Jinwei Yang; Lijun Zhang; Shams ur Rehman; Xiaohua Hao; Lifeng Hou; Chaozhong Zhang; Hongna Li; et al. (Science China Life Sciences, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Effect of surcharge width on evolution of soil arching for active and passive trapdoor - Rui-Xiao Zhang; Dong Su; Hao Xiong; Xing-Tao Lin (European Journal of Environmental and Civil Engineering, 2024)

Improving effect of N-acetylcysteine on growth and intestinal health in juvenile Cyprinus carpio involve the Nrf2/MAPK/NF-κB pathways - Rui Zhu; Deng-Lai Li; Bao-Yuan Zhang; Liang Li; Guo-Jun Shang; Hao-Tong Wang; Zhi-Yong Yang; Xiao-fang Wei; Si-Tong Meng; Si-Ying Liu; Yin-Tao Wang; Li-Fang Wu; et al. (Aquaculture, 2024)

Promotion and monitor wound healing by anthocyanin enhanced light curing ε-poly-l-lysine hydrogel encapsulated Cu-MOF - Xiawei Zhao; Rui Liu; Tiantian Tang; Zihao Liu; Xiaozhi Liu; Kai Yu; Ye Zhang; Hao Wang (Chemical Engineering Journal, 2024)

Positive temperature coefficient material based on silicone rubber/ paraffin/ graphite/ carbon nanotubes for wearable thermal management devices - Jian-Min Hao; Yin-Fa Yang; Yi-Tao Shen; Rui Zhou; Wei Zhang; Hua Chen; Wen-Long Cheng (Chemical Engineering Journal, 2024)

Nitrogen transformations in plastic-film mulched soils - Hao Zhang; Zihao Zhang; Zhe Liu; Tingting Lei; Jinbo Zhang; Christoph Müller; Abeer S. Aloufi; Ekaterina Filimonenko; Yakov Kuzyakov; Rui Jiang (Plant and Soil, 2024)

Identification of key genes involved in lignin and flavonoid accumulation during Tilia tuan seed maturation - Lei Liu; Cui Long; Xuri Hao; Rui Zhang; Chenqi Li; Yuepeng Song (Plant Cell Reports, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

An ontology-driven method for urban building energy modeling - Rui Ma; Qi Li; Botao Zhang; Hao Huang; Chendi Yang (Sustainable Cities and Society, 2024)

Biodegradable film mulching increases soil microbial network complexity and decreases nitrogen-cycling gene abundance - Hao Zhang; Duntao Shu; Jiaqi Zhang; Xuejun Liu; Kai Wang; Rui Jiang (Science of The Total Environment, 2024)

Prediction and explanation of debris flow velocity based on multi-strategy fusion Stacking ensemble learning model - Tianlong Wang; Keying Zhang; Zhenghua Liu; Tianxing Ma; Rui Luo; Hao Chen; Xu Wang; Wei Ge; Hongyue Sun (Journal of Hydrology, 2024)

Fish skin mucosal surface becomes a barrier of antibiotic resistance genes under apramycin exposure - Wenpeng Li; Xiaohan Zhang; Xiaohan Hao; Rui Xin; Ying Zhang; Yongzheng Ma; Zhiguang Niu (Environmental Research, 2024)

Sea surface temperature prediction by stacked generalization ensemble of deep learning - Hao Dai; Famei Lei; Guomei Wei; Xining Zhang; Rui Lin; Weijie Zhang; Shaoping Shang (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Reindeer (Rangifer tarandus) hindlimb joint kinetics: propulsive and energy storage mechanisms and mechanical work - Guoyu Li; Rui Zhang; Hao Pang; Junfeng Wang; Dan Jin; Xumin Sun; Dianlei Han; Zhisong Li; Lige Wen (Polar Biology, 2024)

In situ profiling reveals spatially metabolic injury in the initiation of polystyrene nanoplastic-derived intestinal epithelial injury in mice - Xianan Zhang; Jing Wang; Yuansheng Liu; Hemin Wang; Bin Li; Qing Li; Yi Wang; Yuru Zong; Jiajia Wang; Qingtao Meng; Shenshen Wu; Rongzhang Hao; et al. (Science of The Total Environment, 2024)

Heavy metals potentially drive co-selection of antibiotic resistance genes by shifting soil bacterial communities in paddy soils along the middle and lower Yangtze River - Ya ZHANG; Hao WANG; Minghui HU; Rui CAI; Yuqing MIAO; Xiancan ZHU (Pedosphere, 2024)

Unraveling the impact of environmental provisions in preferential trade agreements on green total factor energy efficiency - Hao Yu; Rui Wang; Aiyu Zhang (Journal of Environmental Management, 2024)

Degradation of quinolone antibiotics by freeze activated periodate: effect of the number of fluorine substituents and DFT calculations - Hao Lin; Yan Zhang; Yucan Liu; Xiuping Sun; Bin Ji; Rui Mei; Tongshuai Liu; Zhonglu Gao; Xin Wang (Journal of Environmental Chemical Engineering, 2024)

MOF derived highly dispersed bimetallic Fe-Ni nitrogen-doped carbon for enhanced peroxymonosulfate activation and tetracycline degradation - Lingyun Jing; Shasha Liu; Tong Wang; Zeqiang Zhang; Xia Zhao; Zhili Sun; Pengbo Hao; Yeqiang Hu; Wenhan Yang; Rui Quan; Xinyong Li; Dongnian Zhang; et al. (Journal of Environmental Chemical Engineering, 2024)

Regulating the defects of MIL-101(Cr) for the efficient and simultaneous determination of eleven plant growth regulators in fresh fruit juice - Rui Cheng; Yiqun Wan; Xuejin Mao; Hao Wan; Fan Liu; Lan Guo; Bingzhen Zhang (Food Chemistry, 2024)

A randomised double-blind placebo-controlled trial of a probiotic combination for manipulating the gut microbiota and managing metabolic syndrome - Rui Xiao; Ying Chen; Xiaofeng Zhu; Linlin Wang; Peijun Tian; Xing Jin; Ming Liang; Zehua Chen; Ting Zhang; Long Qian; Qun Wang; Jianxin Zhao; et al. (Food Bioscience, 2024)

Annual burying of pelletized straw benefits grain amino acid by increasing soil mineral elements: A case study in Northeast China - Peixin Wang; Xiquan Wang; Rui Zong; Xinbo Wang; Haiping Ni; Lumin Liu; Yan Yang; Yubo Hao; Yiteng Zhang; Huancheng Pang; Chunrong Qian (Field Crops Research, 2024)

Improved seed yield and phosphorus accumulation in soybean are associated with the enhanced root exudates in south-west China - Hong-Lan Zhang; Nian Liang; Rui Dong; Chang-An Liu; Chun-Ling Hao; Kadambot H. M. Siddique; Jin He (Plant and Soil, 2024)

A newly defined latest Carboniferous-Permian ridge subduction in the southern Altaids: Insights from adakitic, S-type, and I-type granitoids in the northern East Junggar (NW China) - Jingmin Gan; Wenjiao Xiao; Qigui Mao; Hao Wang; He Yang; Miao Sang; Xiaoliang Jia; Yin Liu; Zhiyong Zhang; Zhou Tan; Rui Li (International Geology Review, 2024)

Effects of dietary bacterial culture of fengycin-producing Bacillus subtilis on growth performance, intestinal and hepatopancreas health, intestinal microbiota and disease resistance of common carp (Cyprinus carpio) - Rui Xia; Shenghui Li; Hongwei Yang; Yajie Zhao; Tsegay Teame; Qiang Hao; Mingxu Xie; Min Li; Qile Chen; Chunling Song; Chao Ran; Yalin Yang; et al. (Aquaculture, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

Advanced oxidation process/coagulation coupled with membrane distillation (AOP/Coag-MD) for efficient ammonia recovery: Elucidating biofouling control performance and mechanism - Wucheng Ma; Rui Han; Wei Zhang; Hao Zhang; Linting Zhao; Lin Chen; Liang Zhu (Journal of Hazardous Materials, 2024)

Synergistic effects of chemical additives and mature compost on reducing H2S emission during kitchen waste composting - Yongdi Liu; Haihou Wang; Hao Zhang; Yueyue Tao; Rui Chen; Sheng Hang; Xiaoyan Ding; Meidi Cheng; Guochun Ding; Yuquan Wei; Ting Xu; Ji Li (Journal of Environmental Sciences, 2024)

Effects of plastic film mulching on yield, water use efficiency, and nitrogen use efficiency of different crops in China: A meta-analysis - Tiantian Huang; Qianxiang Wu; Yangyang Yuan; Xintong Zhang; Ruiqi Sun; Rui Hao; Xiaohua Yang; Congfeng Li; Xiaoliang Qin; Fangqi Song; Charles O. Joseph; Wen Wang; et al. (Field Crops Research, 2024)

Maize cultivar mixtures increase aboveground biomass and grain quality via trait dissimilarity and plasticity - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (European Journal of Agronomy, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Preparation and application of biocontrol formulation of nematode-trapping fungus-Duddingtonia flagrans - Luyao Hao; Yuan Guo; Xiaomin Wang; Mingjuan Gao; Tonghai Liu; Yuan Ma; Yanni Zhang; Qiannan Li; Rui Wang; Xihuo You (Veterinary Parasitology, 2024)

Viologen-based ionic conjugated mesoporous polymer as the electron conveyer for efficient polysulfide trapping and conversion - Hai-Yang Li; Zhong-Shan Li; Gang-Hao Qiu; Rou-Rou Zhang; Ya-Rui Wang; Feng Wang; Ren-Wu Huang; Xiao-Fei Liu; Shuang-Quan Zang (Science Bulletin, 2024)

Oxygen-enriched vacancy spinel Mn-Co oxides by deep thermal reduction for enhanced antibiotics degradation efficiency - Xiai Zhang; Rui Zhou; Ruohong Bi; Tong Wang; Qikui Fan; Hao Zhu; Zhimao Yang; Xiaofei Liu; Chuncai Kong (Journal of Environmental Chemical Engineering, 2024)

Andesitic arc magmas derived from two contrasting mélange origins: Evidence from central Tibetan dioritic porphyries - Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Fang Huang; Ming Xiao; Xiao-Long Ma; Wan-Feng Zhang; Wen-Yu Wang; Mao-Rui Liu (Chemical Geology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

DAE-Mask: a novel deep-learning-based automatic detection model for in-field wheat diseases - Rui Mao; Yuchen Zhang; Zexi Wang; Xingan Hao; Tao Zhu; Shengchang Gao; Xiaoping Hu (Precision Agriculture, 2024)

Weak correlations among leaf thermal metrics, economic traits and damages under natural heatwaves - Qiu-Rui Ning; Qiang Li; Hao-Ping Zhang; Yi Jin; Xue-Wei Gong; Rui-Fang Jiao; Emily Patience Bakpa; Han Zhao; Hui Liu (Science of The Total Environment, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

Towards energy conservation and carbon reduction for wastewater treatment processes: A review of carbon-neutral anaerobic biotechnologies - Xinzheng Zhang; Tianwei Hao; Tao Zhang; Yong Hu; Rui Lu; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Engineering extracellular electron transfer to promote simultaneous brewing wastewater treatment and chromium reduction - Deguang Wu; Baocai Zhang; Sicheng Shi; Rui Tang; Chunxiao Qiao; Teng Li; Jichao Jia; Meiyi Yang; Xiaoguang Si; Yifei Wang; Xi Sun; Dongguang Xiao; et al. (Journal of Hazardous Materials, 2024)

Study and verification on an improved comprehensive prediction model of landslide displacement - Tianlong Wang; Rui Luo; Tianxing Ma; Hao Chen; Keying Zhang; Xu Wang; Zhaowei Chu; Hongyue Sun (Bulletin of Engineering Geology and the Environment, 2024)

Cotton Verticillium wilt monitoring based on UAV multispectral-visible multi-source feature fusion - Rui Ma; Nannan Zhang; Xiao Zhang; Tiecheng Bai; Xintao Yuan; Hao Bao; Daidi He; Wujun Sun; Yong He (Computers and Electronics in Agriculture, 2024)

Investigation of the intrinsic characteristics of two lock-in regions in a 10:1 π-shaped deck - Jiaying Wang; Feng Wang; Rui He; Jiawu Li; Jianming Hao; Jiupeng Zhang; Xiaoming Huang (Ocean Engineering, 2024)

Agronomic performances of biodegradable and non-biodegradable plastic film mulching on a maize cropping system in the semi-arid Loess Plateau, China - Hao ZHANG; Mengqiong CHEN; Ruiquan QIAO; Fan DING; Hao FENG; Rui JIANG (Pedosphere, 2024)

Towards carbon-neutral biotechnologies for rural wastewater: A review of current treatment processes and future perspectives - Xinzheng Zhang; Guangyi Ma; Tao Chen; Churen Yan; Yiheng Chen; Qinye Wang; Xinyu Peng; Wenjie Xu; Tianwei Hao; Tao Zhang; Rui Lu; Dapeng Li; et al. (Journal of Water Process Engineering, 2024)

Magnetic biochar enhanced copper immobilization in agricultural lands: Insights from adsorption precipitation and redox - Wucheng Ma; Rui Han; Wei Zhang; Hao Zhang; Lin Chen; Liang Zhu (Journal of Environmental Management, 2024)

Complexities of regulating climate by promoting marine primary production with ocean iron fertilization - Hai-Bo Jiang; David A. Hutchins; Hao-Ran Zhang; Yuan-Yuan Feng; Rui-Feng Zhang; Wei-Wei Sun; Wentao Ma; Yan Bai; Mark Wells; Ding He; Nianzhi Jiao; Yuntao Wang; et al. (Earth-Science Reviews, 2024)

Superfast hydrous-molten salt erosion to fabricate large-size self-supported electrodes for industrial-level current OER - Jie Deng; Zhichao Wang; Hao Yang; Rui Jian; Yufeng Zhang; Ping Xia; Wei Liu; Olivier Fontaine; Yachao Zhu; Luming Li; Si Chen (Chemical Engineering Journal, 2024)

The Community of Arbuscular Mycorrhizal Fungi in Sugarcane Rhizosphere Soils in Guangxi, China - Jin-Lian Zhang; Juan Song; Yi-Hao Kang; Yun-Ying Wen; Ying-Jie Nong; Qian Wang; Xiao-Juan Qin; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Risk assessment and source identification of soil heavy metals: a case study of farmland soil along a river in the southeast of a mining area in Southwest China - Huajian Chi; Xin Liu; Xiaofang Yang; Rui Zhang; Ting Xia; Yiping Sun; Kan Hu; Fangfang Hao; Yong Liu; Shengchun Yang; Qingwen Deng; Xiaodong Wen (Environmental Geochemistry and Health, 2024)

Boron removal in seawater desalination by progressive freezing-melting - Rui Mei; Tongguo Zhao; Yan Zhang; Hao Lin; Chen Zhao; Lin Lin; Yihong Zou; Yucan Liu (Environmental Science and Pollution Research, 2024)

Diversified cropping systems with complementary root growth strategies improve crop adaptation to and remediation of hostile soils - Wei-Ping Zhang; Surigaoge Surigaoge; Hao Yang; Rui-Peng Yu; Jin-Pu Wu; Yi Xing; Yinglong Chen; Long Li (Plant and Soil, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

Effects of UHPC shear key on strengthening shear performances of wet joint in prefabricated composite beams - Hao Wang; Ning Wang; Xiao-gang Liu; Qing-rui Yue; Jing-liang Yan; Yu Zhang (Engineering Structures, 2024)

Exosome as non-invasive prognostic and diagnostic biomarker and nanovesicle for targeted therapy of non-small cell lung carcinoma - Zhao Yang; Shi Fu; Yongchao Li; Youfeng Liang; Mingxuan Hao; Rui Guo; Changyuan Yu; Zahid Hussain; Jinku Zhang; Haifeng Wang (Chemical Engineering Journal, 2024)

Facile synthesis of bead-chain structured MWCNTs@CeO2 with oxygen vacancies-rich for promoting electrochemical energy storage - Xiao-Man Cao; Jia-Qi Chen; Xin-Rui Zhao; Hao Ge; Daliang Liu; Qiong Wu; Zhi-Jia Sun; Qingguo Zhang (Chemical Engineering Journal, 2024)

Native ApxIIA secreted by Actinobacillus pleuropneumoniae induces apoptosis in porcine alveolar macrophages dependent on concentration and acylation - Hao Tang; Rong Wang; Siqi Pang; Weiyao Han; Qiuhong Zhang; Qiong Fang; Xiabing Chen; Qi Huang; Dexin Qiu; Rui Zhou; Lu Li (Veterinary Microbiology, 2023)

Carbon-neutral potential in treatment of N, N-dimethylformamide-containing industrial wastewater: Comparative investigation of energy conservation, carbon reduction and expenditure between UASB and Fenton process - Xinwei Tan; Yuqin Fan; Xinzheng Zhang; Tianwei Hao; Rong Chen; Tao Zhang; Rui Lu; Jianliang Sun; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2023)

Soil arching in ground with tunnel: Effect of distance between tunnel and trapdoor - Rui-Xiao Zhang; Dong Su; Xing-Tao Lin; Hao Xiong; Xiang-Sheng Chen (Computers and Geotechnics, 2023)

Effects of Mixed Cropping on Sugarcane Growth and the Community of Arbuscular Mycorrhizal Fungi - Ying-Jie Nong; Qian Wang; Juan Song; Jin-Lian Zhang; Xiao-Juan Qin; Yi-Hao Kang; Xiang-Hua Wei; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

The development of ecological civilization in China based on the economic–social–natural complex system - Rui Xiao; Haiguang Hao; Huiyuan Zhang; Yujie Liu; Mengxiao Liu (Ambio, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Widely targeted metabolomics provides insights into the effect of parboiling treatment on the nutritional quality of black rice based on its improved cooking characteristics - Xin Wu; Xingxing Zhang; Min Liu; Tang Tang; Yanhua Li; Hao Chen; Qun Lu; Rui Liu (Journal of Cereal Science, 2023)

On sediment incipient motion of marine cohesive sediments with different bulk densities - Shouqian Li; Mingcheng Zhu; Wei Huang; Hao Zhu; Rui Zhang; Yongjun Lu (Geomorphology, 2023)

Integrative risk assessment method via combining geostatistical analysis, random forest, and receptor models for potentially toxic elements in selenium-rich soil - Hao Wu; Nan Cheng; Ping Chen; Fei Zhou; Yao Fan; Mingxing Qi; Jingyi Shi; Zhimin Zhang; Rui Ren; Cheng Wang; Dongli Liang (Environmental Pollution, 2023)

Peroxymonosulfate enhanced Fe(III) coagulation coupled with membrane distillation for ammonia recovery: Membrane fouling control process and mechanism - Wucheng Ma; Rui Han; Liang Zhu; Wei Zhang; Hao Zhang; Longjie Jiang; Lin Chen (Desalination, 2023)

DEM study on evolution of soil arching in a deep trapdoor in seismic shaking conditions - Rui-Xiao Zhang; Dong Su; Hao Xiong; Xing-Tao Lin; Yuan-Jun Jiang; Xiang-Sheng Chen (Computers and Geotechnics, 2023)

Significantly improved high-temperature capacitive performance in polymer dielectrics utilizing ultra-small carbon quantum dots with Coulomb-blockade effect - Hangchuan Cai; Rui Wang; Bin Gou; Jing Fu; Yujie Zhu; Hao Yang; Jiangang Zhou; Manxi Li; An Zhong; Daoming Zhang; Huasong Xu; Chunhui Bi; et al. (Chemical Engineering Journal, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Multi-layer feature fusion for hyperspectral image classification - Siyuan Hao; Rui Li; Min Zhang; Yuanxin Ye (International Journal of Remote Sensing, 2023)

Dietary acetate promotes growth and nutrients deposition in Nile tilapia (Oreochromis niloticus) through increasing acetyl-CoA-triggered energy production - Wen-Hao Zhou; Samwel M. Limbu; Yuan Luo; Rui-Xin Li; Jiong Ren; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Aquaculture, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

Enhanced nitrogen removal in a pilot-scale AOA-SBFASR system treating municipal wastewater: Process efficiency, microbial community and nitrogen metabolic pathways - Zhi-li Du; Shao-bin Huang; Rui-jian Zhang; Yong-qing Zhang; Hao-tao Dong; Guang-hua Wang; Zhi-min Sun (Journal of Water Process Engineering, 2023)

Effects of multi-frequency ultrasound on inactivating Chironomus kiiensis eggs: Evidence from a case study in drinking water treatment plant - Hai-guang Yuan; Rui-jian Zhang; Ye-qin Xu; Zhi Dang; Yong Hu; Qian-Bin Wang; Hao-tao Dong; Jia-xin Liu; Shu-juan Pu; Zhi-li Du; Ying-shi Liu; Zong-jia Zhang (Journal of Water Process Engineering, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Crop cultivar mixtures stabilize productivity, partly via facilitation, when conditions are less benign - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Jian-Hao Sun; Jian-Hua Zhao; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2023)

The role of trifluoroacetic acid in new particle formation from methanesulfonic acid-methylamine - Yue Hu; Shasha Chen; Shasha Ye; Shuqin Wei; Biwu Chu; Rui Wang; Hao Li; Tianlei Zhang (Atmospheric Environment, 2023)

Impact of nitrogen addition on single and mixed tree leaf litter decomposition depends on N forms in subtropical China - Pan-Pan Wu; Zao Zhang; Rui Li; Jing-Hao Ji; Rong Mao (Applied Soil Ecology, 2023)

Research on the source-detector variance reduction method based on the AIS adjoint Monte Carlo method - Yisheng Hao; Rui Qiu; Zhen Wu; Shenshen Gao; Hui Zhang; Junli Li (Annals of Nuclear Energy, 2023)

An epoxide-based covalent sensor to detect cardiac proteome aggregation in a cardio-oncology model - Hao Jin; Di Shen; Biao Jing; Zhenduo Zhang; Zhiming Wang; Rui Sun; Huaiyue Zhang; Jialu Sun; Haochen Lyu; Yu Liu; Lili Wang (Analytica Chimica Acta, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

Phytoplankton control by stocking of filter-feeding fish in a subtropical plateau reservoir, southwest China - Chaoshuo Zhang; Feng Mei; Bin Luo; Dongxu Zhang; Xinyu Cheng; Yongying Xiong; Jianghui Bao; Rui Duan; Hao Jiang; Erik Jeppesen; Ming Duan (Frontiers in Marine Science, 2023)
Stocking of filter-feeding fish (mainly Hypophthalmichthys molitrix and Aristichthys nobilis ) is a common method used in lakes and reservoirs in (sub)tropical China to control phytoplankton, but the results are ambiguous and lack long-term data to support. We analysed a decade (2010-2020) of monitoring data from a subtropical plateau reservoir, southwest China, to which filter-feeding fish were stocked annually. We found that the total phytoplankton biomass, cyanobacteria biomass and average individual mass of phytoplankton decreased significantly during the study period despite absence of nutrient concentration reduction. However, the grazing pressure of zooplankton on phytoplankton also decreased markedly as judged from changes in the ratio of zooplankton biomass to phytoplankton biomass and Daphnia proportion of total zooplankton biomass. This is likely a response to increasing predation on zooplankton by the stocked fish. Our results also indicated that water temperature, total phosphorus and water level promoted phytoplankton growth. Our results revealed that filter-feeding fish contributed to the decline in the biomass of phytoplankton but that it also had a strong negative effect on the grazing pressure of zooplankton on phytoplankton, even in this deep reservoir where zooplankton may have a better chance of survival through vertical migration. The particular strong effect on zooplankton is most likely due to imbalance of stocking and harvesting of fish. In the management of eutrophic reservoirs, the reduction of external nutrient loading should have highest priority. In highland (low temperature) deep-water eutrophic reservoirs, stocking of filter-feeding fish may help to control filamentous phytoplankton provided that the fish stocking is properly managed. The optimal stocking intensity of filter-feeding fish that can help control phytoplankton in such reservoirs without excessive impact on large-bodied zooplankton is a topic for further elucidation, however.

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Resolved CFD-DEM Simulation of Free Settling of Polyhedral Particles with Various Orientations: Insights Provided by Oscillation Behavior in Quiescent Liquid - Zhimin Zhang; Yuanyi Qiu; Hao Xiong; Rui Tang (Journal of Marine Science and Engineering, 2023)
Particle settling is the process by which particulates move toward the bottom of a liquid, which can affect the sediment transport and energy balance of marine systems. However, the deficiency in understanding the resolved fluid–particle interactions with complex boundaries in the settling process awaits resolution. This study employs a hybrid approach that combines computational fluid dynamics (CFD) with the discrete element method (DEM) to fully simulate the free-settling behavior of polyhedral particles in water. The accuracy of the method is verified by comparing numerical results with experimental data of ellipsoidal particle settling. Two series of tests with horizontal and vertical particle release directions are established to investigate the effects of particle shape features, such as the aspect ratio (AR) and corner (C), on the particles’ mechanical behavior and hydrodynamic characteristics. The results demonstrate that particle shape exerts a substantial influence on fluid resistance, rotational motion, and fluid disturbance throughout the settling process. The maximum velocities in vertically released cases are roughly 1.2–1.3 times greater than those in horizontally released cases. The study highlights the potency of the resolved CFD-DEM method as a robust technique for comprehending fluid–particle phenomena within the marine geotechnical engineering, including sedimentation and erosion of seabed sediments.

Nano-pesticide carrier O-Carboxymethyl chitosan is indigestible in Apis cerana cerana and affects intestinal flora - Sheng-nan Li; Hao Wu; Rui-quan Hou; Jing-tong Zhou; Su-kun Lin; Kun-yu Zhao; Rui-fei Wang; Su-qing Huang; Zhi-xiang Zhang (Science of The Total Environment, 2023)

Soil acidification in a tailing area of ionic rare earth in Southeast China - Zhe Xu; Jin-ling Yang; Yue Zhao; Rui Hao; Gan-lin Zhang (Science of The Total Environment, 2023)

Dynamic probabilistic risk assessment of emergency response for intelligent coal mining face system, case study: Gas overrun scenario - Yan Zhang; Yu-Hao Wang; Xu Zhao; Rui-Peng Tong (Resources Policy, 2023)

Geological ahead-prospecting method while TBM drilling using improved seismic interferometry method: A case - Lei Chen; Lei Hao; Xinji Xu; Fengkai Zhang; Rui Wang (Journal of Applied Geophysics, 2023)

Formation of giant copper deposits in Tibet driven by tearing of the subducted Indian plate - Zengqian Hou; Rui Wang; Haijiang Zhang; Yuanchuan Zheng; Sheng Jin; Hans Thybo; Roberto F. Weinberg; Bo Xu; Zhiming Yang; Ao-Wei Hao; Lei Gao; Letian Zhang (Earth-Science Reviews, 2023)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Bang-Yin Tan; Cai-Feng Ding; Rui-Rong Guo; Jing-Zhi Zhao; Di-Wei Ma; Kun Fan; Lan-Chun Zhang; Rong-Ping Zhang; Wei-Yan Hu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Climate changes in the Hexi Corridor, western China over the past 13.3 ka - Yanzhen Li; Rui Zhang; Hao Long; Peng Cheng; David B. Kemp; Ze Zhang; Chunju Huang; Mengyang Hou; Yue Li; Shizhen Jia; Zhixiang Wang; Liangcheng Tan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Resistant starch formation mechanism of amylosucrase-modified starches with crystalline structure enhanced by hydrothermal treatment - Ren Wang; Pinxin Rui; Tao Wang; Wei Feng; Zhengxing Chen; Xiaohu Luo; Hao Zhang (Food Chemistry, 2023)

Low-Temperature robust MAPbI3 perovskite solar cells with power conversion efficiency exceeding 22.4% - Wenyu Qiu; Yukun Wu; Yichen Wang; Zhiting Yang; Rui Yang; Chenxi Zhang; Yang Hao; Yuying Hao (Chemical Engineering Journal, 2023)

The Regulation of the AMPK/mTOR Axis Mitigates Tendon Stem/Progenitor Cell Senescence and Delays Tendon Aging - Guangchun Dai; Yingjuan Li; Ming Zhang; Panpan Lu; Yuanwei Zhang; Hao Wang; Liu Shi; Mumin Cao; Renwang Shen; Yunfeng Rui (Stem Cell Reviews and Reports, 2023)

A Novel D-π-A Type Fluorescent Probe for Cu2+ Based on Styryl-Pyridinium Salts Conjugating Di-(2-picolyl)amine (DPA) Units - Rui Cao; Mengyu Zhang; Wen Tang; Jing Wu; Meixiang Wang; Xiaoxiao Niu; Zhaodi Liu; Fuying Hao; Huajie Xu (Journal of Fluorescence, 2023)

Lithospheric controls on the formation of the Qilian Shan plateau: Evidence from apatite (U Th)/He and cosmogenic 21Ne results in the Central Qilian Shan - Yan Ma; Jianzhang Pang; Dewen Zheng; Huiping Zhang; Jingxing Yu; Chaopeng Li; Rui Zhang; Yuqi Hao; Ying Wang; Ying Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Enhanced biological stabilization of metal-chelant complexes in the chelator-washed soils by sulfate-reducing bacteria - Guixiang Zhang; Yu Gao; Rui Ren; Xiaofang Guo; Baoshan Xing; Yang Li; Zheyun Zhang; Hao Wu (Journal of Soils and Sediments, 2023)

Large-scale characteristics of thermokarst lakes across the source area of the Yellow River on the Qinghai-Tibetan Plateau - Wen-hui Liu; Guang-hao Zhou; Hai-rui Liu; Qing-peng Li; Chang-wei Xie; Qing Li; Jian-yun Zhao; Qi Zhang (Journal of Mountain Science, 2023)

The distribution and emission of CO2, CH4 and light hydrocarbons in an anticyclonic eddy of the Kuroshio extension - Xiao-Jun Li; Jian Wang; Hao Qiao; Rui-Chen Zhu; Hong-Hai Zhang; Zhao-Hui Chen; Andrew Montgomery; Shan Zheng; Guang-Chao Zhuang (Frontiers in Marine Science, 2023)
Mesoscale eddies are energetic and swirling circulations that frequently occur in the open ocean. The effects of mesoscale eddies on the biogeochemical cycling of climate-relevant gases remain poorly constrained. We investigated the distribution and air-sea fluxes of CO 2 , methane, and five non–methane hydrocarbons (NMHCs) in an anticyclone eddy of Kuroshio Extension during September 2019. Within eddy core, intense stratification hindered the replenishment of nutrients and favored the growth of small-size phytoplankton, such as Prochlorococcus . Seawater pCO 2 decreased from 406.1 μatm at the eddy outside to 377.5 μatm at the eddy core, accompanied by a decrease in surface seawater temperature from 26.7 °C to 25.2 °C. The vertical distribution of methane (0.3-9.9 nmol L -1 ) was influenced by the eddy process, with a maximum at 80 m in the eddy core, which might be attributed to the degradation of phosphonates sustained by Prochlorococcus . The concentrations of five NMHCs (ethane, ethylene, propane, propylene, and isoprene) ranged from 17.2-126.2, 36.7-168.1, 7.5-29.2, 22.6-64.1, 54.5-172.1, 3.5-27.9 pmol L -1 , respectively. Isoprene correlated well with Chl- a concentrations at the eddy core, while no significant correlation was observed at the eddy outside. Air-sea fluxes of CO 2 and isoprene associated with the eddy core were higher than those of the eddy outside, while the maximum ventilation of methane and other NMHCs (ethane, ethylene, propane, and propylene) was found at the eddy outside. Collectively, physical processes such as eddies impact the production and distribution of light hydrocarbons in seawater and further influence their regional emissions to the atmosphere.

Plant litter strengthens positive biodiversity–ecosystem functioning relationships over time - Wei-Ping Zhang; Dario Fornara; Hao Yang; Rui-Peng Yu; Ragan M. Callaway; Long Li (Trends in Ecology & Evolution, 2023)

High magnesian schist, granitic gneiss, amphibolite and monzogneiss in the eastern Ama Drime Massif in South Tibet (China): A rifted Paleoproterozoic arc fringed the western Columbia supercontinent? - Rui Li; Wenjiao Xiao; Qigui Mao; Ji'en Zhang; Songjian Ao; Dongfang Song; Zhou Tan; Hao Wang; Saunak Bhandari (Precambrian Research, 2023)

Theoretical study the electrocatalytic performance and mechanism of novel designed electrocatalyst Ru@2DMs for CO2RR - Linxia Cui; Ke Shi; Mingyuan Zhang; Jiuwen Guo; Zhe Yan; Haigang Hao; Rui Gao (Fuel, 2023)

Seismic damage characteristics and evaluation of aboveground-underground coupled structures - Gang Li; Han Zhang; Rui Wang; Zhi-Qian Dong; Ding-Hao Yu (Engineering Structures, 2023)

Centrifuge and numerical modeling of h-type anti-slide pile reinforced soil-rock mixture slope - Hao Zhang; Hao-feng Xing; Dao-rui Xue; Dwayne Tannant (Journal of Mountain Science, 2023)

New insight into the role of the emulsified diesel droplet size in low rank coal flotation - Jincheng Liu; Rui Zhang; Xicheng Bao; Yesheng Hao; Xiahui Gui; Yaowen Xing (Fuel, 2023)

Highly stability Cu+ species in hollow Cu2O nanoreactors by modulating cavity size for CO2 electroreduction to C2+ products - Rui Zhang; Feifei Chen; Haokun Jin; Yong Zhang; Xiaoya Hao; Yingda Liu; Tianming Feng; Xinghua Zhang; Zunming Lu; Weihua Wang; Feng Lu; Hong Dong; et al. (Chemical Engineering Journal, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Determination of lead in Gentiana rigescens and evaluation of the effect of lead exposure on the liver protection of the natural medicine - Rui Zhang; Caixia Yan; Xiaofang Yang; Kan Hu; Fangfang Hao; Shengchun Yang; Qingwen Deng; Zhenjuan Duan; Yong Liu; Xiaodong Wen (Analytica Chimica Acta, 2023)

Study on non-point source pollution characteristics under different spatial scales: a case study of Hanjiang River Basin, China - Ya-jiao Li; Jia-ping Wang; Zi-hang Zhang; Gai-rui Hao; Ya-fang Li; Jia-ke Li (Environmental Science and Pollution Research, 2023)

Diffusion simulation and risk assessment model establishment of chlorine gas leakage based on terrain conditions - Xiao-ting Ren; Xiao-ling Ma; Jiang-zheng Liu; Rui Liu; Chen-qian Zhao; Hao Wu; Zhao Wang; Chun-xu Hai; Xiao-di Zhang (Environmental Science and Pollution Research, 2023)

Circ_0021573 acts as a competing endogenous RNA to promote the malignant phenotypes of human ovarian cancer cells - Lifang Liu; Bingkai Han; Lixia Liu; Hongying Cui; Hao Liu; Rui Jia; Xiaoyan Zhang; Xiaoxiao Lu (Reproductive Biology, 2023)

SUMOylation-modified Pelota-Hbs1 RNA surveillance complex restricts the infection of potyvirids in plants - Linhao Ge; Buwei Cao; Rui Qiao; Hongguang Cui; Shaofang Li; Hongying Shan; Pan Gong; Mingzhen Zhang; Hao Li; Aiming Wang; Xueping Zhou; Fangfang Li (Molecular Plant, 2023)

Variability of fuel consumption and CO2 emissions of a gasoline passenger car under multiple in-laboratory and on-road testing conditions - Boya Zhou; Liqiang He; Shijian Zhang; Rui Wang; Luowei Zhang; Mengliang Li; Yu Liu; Shaojun Zhang; Ye Wu; Jiming Hao (Journal of Environmental Sciences, 2023)

Sulfite altered permanganate effects on acetate-enriched short-chain fatty acids production during sludge anaerobic fermentation - Lijuan Wu; Rui Zhu; Xiaoxia Han; Yan Chen; Zhen Long; Hao Dong; Xiaojiang Chen; Yang Wu; Yinglong Su; Zhengyong Zhang; Jingyang Luo (Bioresource Technology, 2023)

Research in superior bearing performance of the ostrich tarsometatarsus based on its structural features - Rui Zhang; Xumin Sun; Hao Pang; Shuliang Xue; Hua Zhang; Zhenyu Hu; Meng Zou (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

High cholesterol intake remodels cholesterol turnover and energy homeostasis in Nile tilapia (Oreochromis niloticus) - Rui-Xin Li; Ling-Yun Chen; Samwel M. Limbu; Yu-Cheng Qian; Wen-Hao Zhou; Li-Qiao Chen; Yuan Luo; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Marine Life Science & Technology, 2023)
The roles of dietary cholesterol in fish physiology are currently contradictory. The issue reflects the limited studies on the metabolic consequences of cholesterol intake in fish. The present study investigated the metabolic responses to high cholesterol intake in Nile tilapia ( Oreochromis niloticus ), which were fed with four cholesterol-contained diets (0.8, 1.6, 2.4 and 3.2%) and a control diet for eight weeks. All fish-fed cholesterol diets showed increased body weight, but accumulated cholesterol (the peak level was in the 1.6% cholesterol group). Then, we selected 1.6% cholesterol and control diets for further analysis. The high cholesterol diet impaired liver function and reduced mitochondria number in fish. Furthermore, high cholesterol intake triggered protective adaptation via (1) inhibiting endogenous cholesterol synthesis, (2) elevating the expression of genes related to cholesterol esterification and efflux, and (3) promoting chenodeoxycholic acid synthesis and efflux. Accordingly, high cholesterol intake reshaped the fish gut microbiome by increasing the abundance of Lactobacillus spp. and Mycobacterium spp., both of which are involved in cholesterol and/or bile acids catabolism. Moreover, high cholesterol intake inhibited lipid catabolic activities through mitochondrial β-oxidation, and lysosome-mediated lipophagy, and depressed insulin signaling sensitivity. Protein catabolism was elevated as a compulsory response to maintain energy homeostasis. Therefore, although high cholesterol intake promoted growth, it led to metabolic disorders in fish. For the first time, this study provides evidence for the systemic metabolic response to high cholesterol intake in fish. This knowledge contributes to an understanding of the metabolic syndromes caused by high cholesterol intake or deposition in fish.

Dietary sodium acetate improves high-fat diet utilization through promoting differential nutrients metabolism between liver and muscle in Nile tilapia (Oreochromis niloticus) - Wen-Hao Zhou; Samwel M. Limbu; Rui-Xin Li; Yuan Luo; Jiong Ren; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Aquaculture, 2023)

How seasonality affects the environmental performance of fresh appetite: Insights from cherry consumption in China - Xin Xiong; Junyi Shen; Yan Hao; Lixiao Zhang; Rui Zhao; Shoujuan Tang; Xinqing Li; Zhimin Shi (Journal of Environmental Management, 2023)

Axial compression behaviour of round-ended recycled aggregate concrete-filled steel tube stub columns (RE-RACFST): Experiment, numerical modeling and design - Hui Zhao; Wen-Hao Zhang; Rui Wang; Chuan-Chuan Hou; Dennis Lam (Engineering Structures, 2023)

Friction induced mechanochemistry: self-adaptive lubrication through in-situ tribo-click system - Rui Dong; Yunlei Zhang; Hao-Zhe Xu; Luyao Bao; Shuanhong Ma; Xin-Gang Wang; Qiangliang Yu; Meirong Cai; Feng Zhou; Weimin Liu (Chemical Engineering Journal, 2023)

Redox of anionic and cationic radical intermediates in a bipolar polyimide COF for high-performance dual-ion organic batteries - Shuai Gu; Jingjing Chen; Rui Hao; Xi Chen; Zhiqiang Wang; Iftikhar Hussain; Guiyu Liu; Kun Liu; Qingmeng Gan; Zhiqiang Li; Hao Guo; Yingzhi Li; et al. (Chemical Engineering Journal, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Territorial function differentiation and its comprehensive regionalization in China - Jie Fan; Kan Zhou; Kerong Sheng; Rui Guo; Dong Chen; Yafei Wang; Hanchu Liu; Zheng Wang; Yong Sun; Jie Zhang; Jianxiong Wu; Hao Zhao (Science China Earth Sciences, 2023)

A Medicago truncatula lncRNA MtCIR1 negatively regulates response to salt stress - Rui Tian; Xiaohan Sun; Cuimei Liu; Jinfang Chu; Mingui Zhao; Wen-Hao Zhang (Planta, 2023)

MicroRNA-588 regulates the invasive, migratory and vasculogenic mimicry-forming abilities of hypoxic glioma cells by targeting ROBO1 - Rui Yu; Rongrong Zhao; Xiaopeng Sun; Zongpu Zhang; Shaobo Wang; Xiao Gao; Zhongzheng Sun; Hao Xue; Gang Li (Molecular Biology Reports, 2023)
Background The microenvironment of hypoxia is an important factor contributing to the development of glioblastoma (GBM). MicroRNA-588 and its potential target Roundabout-directed receptor 1 (ROBO1) have been reported to promote tumor invasion and proliferation in diseases such as gastric, pancreatic and hepatocellular carcinoma, while their function in GBM and response to hypoxic states remain elusive. Methods A microarray was leveraged to identify differentially expressed microRNAs in U251 glioma cells cultured under normoxic and hypoxic conditions. The expression of miR-588 was assessed using quantitative real-time PCR (qRT‒PCR). Gain- and loss-of-function studies were used to evaluate the role of miR-588 under hypoxic and normoxic conditions. Cell invasion, migration, proliferation, and vasculogenic mimicry (VM) formation experiments were performed. The relationship between miR-588 and ROBO1 was confirmed using western blot and luciferase reporter assays. Intracranial xenograft tumor mouse models were used to study the function of miR-588 in vivo. Results The expression of miR-588 was significantly upregulated in hypoxic glioma cells relative to normoxic glioma cells. miR-588 inhibited the invasive, migratory and VM-forming abilities of glioma cells in vitro and in vivo. Mechanistically, roundabout guidance receptor 1 (ROBO1) is a direct, functionally relevant target of miR-588 in glioma. ROBO1 knockdown suppressed the expression of matrix metallopeptidase 2 (MMP2) and matrix metallopeptidase 9 (MMP9), thereby inhibiting the invasive, migratory and VM-forming abilities of glioma. Conclusions MiR-588 regulated the behaviors of hypoxic glioma cells by targeting ROBO1. miR-588 can be used as a prognostic marker for glioma and has potential implications in glioma gene therapy.

Orbital and Millennial-Scale Climate Variability over the Past 76 ka in the Western Tarim Basin, Northwest China - Rui Zhang; Qiuzhen Yin; Weihua Nai; Zhixiang Wang; Hao Lu; Chunju Huang; Yansheng Gu; Lin Li; Yusong Wang; Linjing Liu (Journal of Earth Science, 2023)

Intercrop overyielding weakened by high inputs: Global meta-analysis with experimental validation - Shuang-Guo Zhu; Hao Zhu; Rui Zhou; Wei Zhang; Wei Wang; Yi-Ning Zhou; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; Hong-Yan Tao; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Effects of chemical additives and mature compost on reducing nitrogen loss during food waste composting - Shangao Xiong; Yongdi Liu; Hao Zhang; Shaoqi Xu; Songrong Li; Xinqi Fan; Rui Chen; Guochun Ding; Ji Li; Yuquan Wei (Environmental Science and Pollution Research, 2023)

Effects of dietary methionine on growth and body composition, indicators of digestion, protein metabolism and immunity, and resistance to heat stress of abalone Haliotis discus hannai - Hao Chen; Wenhao Fan; Hongyang Zhang; Panpan Yue; Rui Wang; Wenbing Zhang; Kangsen Mai (Aquaculture, 2023)

Evaluation of the pathogenesis of non-typical strain with α-hemolysin, Vibrio parahaemolyticus 353, isolated from Chinese seafood through comparative genome and transcriptome analysis - Fei Zha; Rui Pang; Shixuan Huang; Jumei Zhang; Juan Wang; Moutong Chen; Liang Xue; Qinghua Ye; Shi Wu; Meiyan Yang; Qihui Gu; Yu Ding; et al. (Marine Pollution Bulletin, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Characteristics and origin of Lower Triassic Feixianguan Formation dolostones on the west side of Kaijiang–Liangping Trough, northeastern Sichuan Basin, China - Ling Zhou; Guangwei Wang; Ya Zhang; Yanping Qiao; Fang Hao; Rui Xu; Li Quan; Ping Wang (Marine and Petroleum Geology, 2023)

Learn then match: A fast coarse-to-fine depth image-based indoor localization framework for dark environments via deep learning and keypoint-based geometry alignment - Qing Li; Rui Cao; Jiasong Zhu; Hao Fu; Baoding Zhou; Xu Fang; Sen Jia; Shenman Zhang; Kanglin Liu; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Identification of high iron–chelating peptides with unusual antioxidant effect from sea cucumbers and the possible binding mode - Chaozhong Fan; Xiaofan Ge; Junyu Hao; Tao Wu; Rui Liu; Wenjie Sui; Jieting Geng; Min Zhang (Food Chemistry, 2023)

All-in-one additive enables defect passivated, crystallization modulated and moisture resisted perovskite films toward efficient solar cells - Chuanming Tian; Yu Zhao; Xuefei Han; Bin Li; Yichuan Rui; Hao Xiong; Yu Qiu; Wei An; Kerui Li; Chengyi Hou; Yaogang Li; Hongzhi Wang; et al. (Chemical Engineering Journal, 2023)

Enhancing structural and cycle stability of Prussian blue cathode materials for calcium-ion batteries by introducing divalent Fe - Chong-Yu Du; Zi-Hao Zhang; Xun-Lu Li; Rui-Jie Luo; Cui Ma; Jian Bao; Jie Zeng; Xuan Xu; Fei Wang; Yong-Ning Zhou (Chemical Engineering Journal, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

Leakage Fault Diagnosis of Lifting and Lowering Hydraulic System of Wing-Assisted Ships Based on WPT-SVM - Ranqi Ma; Haoyang Zhao; Kai Wang; Rui Zhang; Yu Hua; Baoshen Jiang; Feng Tian; Zhang Ruan; Hao Wang; Lianzhong Huang (Journal of Marine Science and Engineering, 2022)
Wing-assisted technology is an effective way to reduce emissions and promote the decarbonization of the shipping industry. The lifting and lowering of wing-sail is usually driven by hydraulic system. Leakage, as an important failure form, directly affects the safety as well as the functioning of hydraulic system. To increase the system reliability and improve the wing-assisted effect, it is essential to conduct leakage fault diagnosis of lifting and lowering hydraulic system. In this paper, an AMESim simulation model of lifting and lowering hydraulic system of a Very Large Crude Carrier (VLCC) is established to analyze the operation characteristics of the hydraulic system. The effectiveness of the model is verified by the operation data of the actual hydraulic system. On this basis, a wavelet packet transform (WPT)-based sensitive feature extracting method of leakage fault for the hydraulic system is proposed. Subsequently, a support vector machine (SVM)-based multi-classification model and diagnosis method of leakage fault are proposed. The study results show that the proposed method has an accuracy of as high as 97.5% for six leakage fault modes. It is of great significance for ensuring the reliability of the wing-sail operation and improving the utilization rate of the offshore wind resources.

Effects and mechanism of ultrasound treatment on Chironomus kiiensis eggs - Bo-dong Liu; Hao-tao Dong; Hong-wei Rong; Rui-jian Zhang (Environmental Science and Pollution Research, 2022)

Ferroptosis induced by the biocontrol agent Pythium oligandrum enhances soybean resistance to Phytophthora sojae - Yang Cheng; Huanxin Zhang; Wenyi Zhu; Qing Li; Rui Meng; Kun Yang; Ziqian Guo; Ying Zhai; Haijing Zhang; Rui Ji; Hao Peng; Daolong Dou; et al. (Environmental Microbiology, 2022)
Ferroptosis is a newly discovered form of cell death accompanied by iron accumulation and lipid peroxidation. Both biotic and abiotic stresses can induce ferroptosis in plant cells. In the case of plant interactions with pathogenic Phytophthora oomycetes, the roles of ferroptosis are still largely unknown. Here, we performed transcriptome analysis on soybean plants treated with the biocontrol agent Pythium oligandrum , a soilborne and non‐pathogenic oomycete capable of inducing plant resistance against Phytophthora sojae infection. Expression of homologous soybean genes involved in ferroptosis and resistance was reprogrammed upon P. oligandrum treatment. Typical hallmarks for characterizing ferroptosis were detected in soybean hypocotyl cells, including decreased glutathione (GSH) level, accumulation of ferric ions, and lipid peroxidation by reactive oxygen species (ROS). Meanwhile, ferroptosis‐like cell death was triggered by P. oligandrum to suppress P. sojae infection in soybean. Protection provided by P. oligandrum could be attenuated by the ferroptosis inhibitor ferrostatin‐1 (Fer‐1), suggesting the critical role of ferroptosis in soybean resistance against P. sojae . Taken together, these results demonstrate that ferroptosis is a P. oligandrum ‐inducible defence mechanism against oomycete infection in soybean.

Impact of climate change on long-term variations of small yellow croaker (Larimichthys polyactis) winter fishing grounds - Rui Zhang; Yang Liu; Hao Tian; Shuhao Liu; Kaiwei Zu; Xinmei Xia (Frontiers in Marine Science, 2022)
Small yellow croaker ( Larimichthys polyactis ) is one of the key demersal species with high economic values and wide distribution in the China Seas. In this study, a Winter Fishing ground Abundance Index (WFAI) was developed by using fisheries survey data in 1971–1982 and used as the response variable to investigate the impacts of environmental variables, including surface current velocity (SCV), sea surface salinity (SSS), sea surface temperature (SST), and depth (DE). A total of 45 combinatorial generalized additive models (GAMs), generalized linear models (GLMs), and random forest models (RFs) were used to select the optimal WFAI prediction. The final WFAI distribution results showed that the winter fishing ground hotspots of small yellow croaker were mainly distributed between 11°C and 16°C isotherms and between 50-m and 100-m isobaths, and the area of winter fishing ground hotspots (WFHA) significantly decreased and the hotspots tended to move northward over the past 50 years. The shape of hotspots was strongly affected by temperature fronts and salinity fronts. Analysis with the climate indices revealed that the Atlantic Multidecadal Oscillation (AMO) might have a large influence on the distribution of small yellow croaker by affecting SST and SSS in the China Seas more than the Pacific Decadal Oscillation (PDO), North Pacific Gyre Oscillation (NPGO), and Arctic Oscillation Index (AOI). The future prediction based on two extreme scenarios (RCP2.6 and RCP8.5) indicated that the hotspots would obviously move northward. These findings will serve effectively the fishery resources monitoring, management, and evaluation of small yellow croaker in the China Seas.

Belowground processes and sustainability in agroecosystems with intercropping - Rui-Peng Yu; Hao Yang; Yi Xing; Wei-Ping Zhang; Hans Lambers; Long Li (Plant and Soil, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Bionic study of the cushioning and energy-saving joints of leg of the walking robot - Rui Zhang; Wenchao Dong; Lujiang Liu; Xuemei Ju; Hao Pang; Qingqiu Cao; Lige Wen (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)

Two new cytotoxic cycloartane triterpenoids from Aphanamixis polystachya (Wall.) R. N. Parker - Yi-ting Wang; Shi-rui Fan; Jie-yun Cai; Jing-jing Guo; Xin-fang Zhang; Bi-juan Yang; Xiao-jiang Hao; Duo-zhi Chen (Natural Product Research, 2022)

Laboratory and centrifugal model tests on failure mechanism of canal slopes under cyclic action of wetting–drying - Rui Zhu; Ying-hao Huang; Chen Zhang; Wan-li Guo; Hao Chen (European Journal of Environmental and Civil Engineering, 2022)

TRIP13 knockdown inhibits the proliferation, migration, invasion, and promotes apoptosis by suppressing PI3K/AKT signaling pathway in U2OS cells - De-Chen Yu; Xiang-Yi Chen; Hai-Yu Zhou; De-Quan Yu; Xiao-Lei Yu; Yi-Cun Hu; Rui-Hao Zhang; Xiao-Bo Zhang; Kun Zhang; Mao-Qiang Lin; Xi-Dan Gao; Tao-Wen Guo (Molecular Biology Reports, 2022)

Epigallocatechin‐3‐gallate inhibits replication of white spot syndrome virus in the freshwater crayfish Procambarus clarkii - Yitong Zhang; Jinxuan Wen; Yao Xu; Hao Wang; Liqun Lu; Rui Song; Jixing Zou (Journal of Fish Diseases, 2022)
The freshwater crayfish Procambarus clarkii is native to North America and Mexico, and it was introduced to China in 1929. The production and consumption of P. clarkii in China are the highest worldwide, reaching 208.96 million tons in 2020. The white spot syndrome virus (WSSV) is a major pathogen that affects shrimp, crayfish, crabs and lobsters, and it has caused widespread loss to the P. clarkii industry. Epigallocatechin‐3‐gallate (EGCG), a small‐molecule compound, has a multitude of biological functions and the ability to bind to the 37 kDa/67 kDa laminin receptor ( LamR ). EGCG has potential antiviral effects against WSSV. In this study, we evaluated the potential anti‐WSSV applications of EGCG in P. clarkii . We demonstrated that various concentrations (10 μg/g·bw, 20 μg/g·bw and 40 μg/g·bw) of EGCG can suppress WSSV infection in P. clarkii . Histopathological examination revealed no characteristic pathological changes due to EGCG administration in P. clarkii tissues. Furthermore, pharmacokinetics studies of EGCG in P. clarkii revealed its rapid absorption (T max = 2 h), and the peak concentrations of EGCG were 73.78 µg/g in the liver and 24.87 µg/g in the muscle. Our results indicate the high potential applications of EGCG against WSSV in P. clarkii .

Two new threonine-containing metabolites from fungus Curvularia inaequalis strain HS-FG-257 - Shao-Yong Zhang; Jian-Song Li; Hui Zhang; Huan Qi; Rui-Jun Wang; Chou-Fei Wu; Li-Qin Zhang; An-Liang Chen; Ji-Dong Wang; Zhi-Kui Hao (Natural Product Research, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

Loganin ameliorates depression-like behaviors of mice via modulation of serotoninergic system - Chen-Hao Pan; Cong-Yuan Xia; Yu Yan; Yan Han; Rui Shi; Jun He; Ze-Xing Wang; Yu-Ming Wang; Wei-Ku Zhang; Jie-Kun Xu (Psychopharmacology, 2021)

Associations between air pollution exposure and birth defects: a time series analysis - Shu Sun; Qi Zhang; Xinmiao Sui; Liu Ding; Jie Liu; Mei Yang; Qihong Zhao; Chao Zhang; Jiahu Hao; Xiujun Zhang; Shilei Lin; Rui Ding; et al. (Environmental Geochemistry and Health, 2021)

Light and high-strength structure inspired by the characteristics of double-nutrient foramens in intertarsal joint of ostrich - Rui Zhang; Chengjin Wang; Shichao Fan; Dong Li; Hao Pang; Lei Ling; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Tracing Nutrients and Organic Matter Changes in Eutrophic Wenchang (China) and Oligotrophic Krka (Croatia) Estuaries: A Comparative Study - You-You Hao; Zhuo-Yi Zhu; Fu-Tao Fang; Tihana Novak; Milan Čanković; Enis Hrustić; Zrinka Ljubešić; Ming Li; Jin-Zhou Du; Rui-Feng Zhang; Blaženka Gašparović (Frontiers in Marine Science, 2021)
Estuaries modify the concentration and composition of riverine nutrients and organic matter (OM), which eventually determine the riverine flux effect to coasts. Nutrients, organic carbon (OC), pigments, and amino acids (AAs) from the samples collected in the eutrophic Wenchang River Estuary (WRE) in China and the oligotrophic Krka River Estuary (KRE) in Croatia were analyzed in order to have a better understanding of how estuaries regulate terrestrial materials. We found a clear increase of dissolved inorganic nitrogen (DIN) concentration and its subsequent decrease due to the removal of DIN (over 100 μM) in the WRE, whereas DIN showed minor variation lengthwise in the KRE, i.e., with the salinity changes, ranging between 1.0 and 5.8 μM. The elevated algae-derived OC, dissolved organic nitrogen, and particulate AAs nitrogen suggest that the OM assimilation may explain approximately one-third of the DIN removal in the WRE, whereas in the oligotrophic KRE, such inorganic to organic transformation is not likely to be significant. Due to the prominent estuarine nitrogen removal/assimilation process, DIN/dissolved inorganic phosphorus (DIP) ratio was as high as 425 in the upper WRE under strong riverine influence, but it declined to as low as 5.4 at the mouth of WRE, that is even lower than DIN/DIP ratio at the mouth of oligotrophic KRE (12). When compared with other rivers worldwide, the Wenchang River showed high nutrients and organic carbon yields. Given the contrasting estuarine process (e.g., DIN removal) between the KRE and the WRE, apparent high nutrient yield from eutrophic rivers should be viewed with caution in ocean studies as the final impact to coastal zone could be similar to the oligotrophic rivers like the KRE.

Insights into heat response mechanisms in Clematis species: physiological analysis, expression profiles and function verification - Hao Zhang; Changhua Jiang; Rui Wang; Long Zhang; Ruonan Gai; Siyuan Peng; Yi Zhang; Chanjuan Mao; Yuxia Lou; Jianbin Mo; Shucheng Feng; Feng Ming (Plant Molecular Biology, 2021)

A new dineolignan with anti- β -amyloid aggregation activity from the fruits of crataegus pinnatifida bge - Peng Zhao; Li-Li Lou; Hao Zhang; Rui Guo; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2021)

3D DEM analysis on tractive trafficability of a lunar rover wheel with bionic wheel lugs - Hao Pang; Rui Zhang; Ping Ge; Fang Liu; Chengjin Wang; Wenchao Dong; Tao Li; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Discussion on Some Topical Issues of Water Prevention and Control in Coal Mines - Shuning Dong; Wenzhong Zhang; Wanfang Zhou; Rui Chai; Hao Wang; Chunhu Zhao; Xingling Dong; Qiangmin Wang (Mine Water and the Environment, 2021)

Different physiological responses of C3 and C4 plants to nanomaterials - Tonghao Bai; Peng Zhang; Zhiling Guo; Andrew J. Chetwynd; Mei Zhang; Muhammad Adeel; Mingshu Li; Kerui Guo; Ruize Gao; Jianwei Li; Yi Hao; Yukui Rui (Environmental Science and Pollution Research, 2021)

Design of the bionic wheel surface based on the friction characteristics of ostrich planta - Hao Pang; Hua Zhang; Rui Zhang; Wenchao Dong; Tao Li; Songsong Ma; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Ca2+/Calmodulin-NOS/NO-TNFs Pathway Hallmarks the Inflammation Response of Oyster During Aerial Exposure - Hao Chen; Lusheng Xin; Lin Wang; Huan Zhang; Rui Liu; Hao Wang; Xue Qiao; Lingling Wang; Linsheng Song (Frontiers in Marine Science, 2021)
Aerial exposure (emersion) due to the periodical ebb and flow of tides is a major stressor for intertidal organisms and a key environmental factor in shaping their local communities. Oysters are among the most emersion-tolerant mollusk species and can survive for several days under aerial exposure. Noticeably, overwhelming inflammation responses could occur during the emersion stress. However, mechanisms beneath the activation and modulation of emersion-induced inflammation response have remained largely unknown. Ca 2+ is an important intracellular second messenger that plays indispensable roles in inflammation response by cooperation with calmodulin (CaM) genes. Here, we showed that intracellular Ca 2+ accumulates rapidly in oyster hemocytes during emersion stress along with the changes in the protein levels of three CaM genes, which function as intracellular sensors of Ca 2+ . As downstream effector of Ca 2+ /CaM complex, nitric oxide synthase (NOS) activity in hemocytes was enhanced during the emersion stress, facilitating a greater production of nitrite oxide (NO). Augmentation of NO concentration was associated with the increased mRNA expression levels of two oyster cytokines (CgTNFs) during aerial exposure. The robust accumulation of cytokines and severe injury of tissues in oysters have been regarded as potential cause and marker of their death in prolonged emersion stress. Here, both the expression levels of CgTNFs and the tissue injuries of oysters were attenuated when Ca 2+ /CaM complex or NOS activity were repressed in vivo during the emersion stress. These findings indicate that Ca 2+ /CaM-NOS/NO-CgTNFs pathway is critically involved in the emersion-induced inflammation response in oysters and plays a role in the resistance against long-term aerial exposure.

Partial recovery of disturbed V-J pairing profiles of T-cell receptor in people living with HIV receiving long-term antiretroviral therapy - Guoli Li; Jiarui Li; Henghui Zhang; Yu Zhang; Di Liu; Yu Hao; Junyan Han; Juan Du; Liuluan Zhu; Yongqin Zeng; Bei Li; Rui Li; et al. (Science China Life Sciences, 2021)

Quantitative assessment of non-point source pollution load of PN/PP based on RUSLE model: a case study in Beiluo River Basin in China - Gai-rui Hao; Jia-ke Li; Shu Li; Kang-bin Li; Zi-hang Zhang; Huai-en Li (Environmental Science and Pollution Research, 2020)

Bioaccumulation of ytterbium oxide nanoparticles insinuate oxidative stress, inflammatory, and pathological lesions in ICR mice - Muhammad Adeel; Jin Tingting; Tariq Hussain; Xiao He; Muhammad Arslan Ahmad; Muhammad Kashif Irshad; Noman Shakoor; Peng Zhang; Xie Changjian; Yi Hao; Zhang Zhiyong; Rabia Javed; et al. (Environmental Science and Pollution Research, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Candidate proteins involved in the calyx abscission process of ‘Kuerlexiangli’ (Pyrus sinkiangensis Yu) identified by iTRAQ analysis - Xin Gong; Jianping Bao; Jing Chen; Kaijie Qi; Zhihua Xie; Weikang Rui; Guowei Hao; Katsuhiro Shiratake; Shahrokh Khanizadeh; Shaoling Zhang; Shutian Tao (Acta Physiologiae Plantarum, 2020)

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Clinical strategies for differentiating IgG4-related cholecystitis from gallbladder carcinoma to avoid unnecessary surgical resection - Rui Zhang; Hao-Ming Lin; Zhao-Xi Cai; Su-Juan Du; Hong Zeng; Lei-Bo Xu; Jie Wang; Chao Liu (Science China Life Sciences, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Plasma Endostatin Levels at Acute Phase of Ischemic Stroke Are Associated with Post-Stroke Cognitive Impairment - Sifan Qian; Ruyi Li; Chenhuan Zhang; Rui Zhang; Daoxia Guo; Xiaoqing Bu; Aili Wang; Hao Peng; Jing Chen; Yonghong Zhang; Jiang He; Tan Xu; et al. (Neurotoxicity Research, 2020)

Bionic design in anti-bending and lightweight tube based on the tarsometatarsus of ostrich - Rui Zhang; Hao Pang; Dianlei Han; Shuliang Xue; Lei Jiang; Dong Li; Lige Wen; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2020)

Design and Experiment of a Plateau Data-Gathering AUV - Hao Xu; Guo-Cheng Zhang; Yu-Shan Sun; Shuo Pang; Xiang-Rui Ran; Xiang-Bin Wang (Journal of Marine Science and Engineering, 2019)
The design, control, and implementation of an autonomous underwater vehicle (AUV) for collecting hydrological information from plateau rivers and lakes are presented in this paper. The hardware and software structures of the control system were previously described. A novel sliding mode controller (SMC) with combinational reaching law of vertical hovering motion is proposed to improve the robustness and stability. The S-plane control, a nonlinear controller with little parameters, is used in the horizontal motion. Besides, the navigation strategy based on the dead-reckoning algorithm, a path tracking based on the light-of-sight (LOS) algorithm, and a control allocation strategy considering saturation are present. Finally, experiments were performed in a tank and in a river in the Qinghai–Tibet Plateau to prove the feasibility and reliability of the AUV system.

Poly-PR in C9ORF72-Related Amyotrophic Lateral Sclerosis/Frontotemporal Dementia Causes Neurotoxicity by Clathrin-Dependent Endocytosis - Rui Wang; Xingyun Xu; Zongbing Hao; Shun Zhang; Dan Wu; Hongyang Sun; Chenchen Mu; Haigang Ren; Guanghui Wang (Neuroscience Bulletin, 2019)

Antioxidant defense against rust infection in the leaf tissue of Malus crabapple - Yudan Duan; Suxiao Hao; Rui Luo; Yanfen Lu; Ge Li; Jie Zhang; Ji Tian; Yuncong Yao (Acta Physiologiae Plantarum, 2019)

QsvR integrates into quorum sensing circuit to control Vibrio parahaemolyticus virulence - Yiquan Zhang; Linghui Hu; Yue Qiu; George Osei‐Adjei; Hao Tang; Ying Zhang; Rui Zhang; Xiumei Sheng; Shungao Xu; Wenhui Yang; Huiying Yang; Zhe Yin; et al. (Environmental Microbiology, 2019)
Summary Vibrio parahaemolyticus , the leading cause of seafood‐associated gastroenteritis worldwide, requires the two type‐III secretion systems (T3SS1 and T3SS2) and a thermostable direct hemolysin (encoded by tdh1 and tdh2 ) for full virulence. The tdh genes and the T3SS2 gene cluster constitute an 80 kb pathogenicity island known as Vp‐PAI located on the chromosome II. Expression of T3SS1 and Vp‐PAI is regulated in a quorum sensing (QS)‐dependent manner but its detailed mechanisms remain unknown. Herein, we show that three factors (QS regulators AphA and OpaR and an AraC‐type transcriptional regulator QsvR) form a complex regulatory network to control the expression of T3SS1 and Vp‐PAI genes. At low cell density (LCD), whereas Vp‐PAI expression is repressed, T3SS1 genes are induced by AphA, which directly binds (an operator region of) the exsBAD‐vscBCD operon. At high cell density (HCD), the bacterium turns off T3SS1 expression by replacing AphA with OpaR, triggering the induction of Vp‐PAI. Furthermore, QsvR binds to the regulatory regions of all the tested T3SS1 and Vp‐PAI genes to activate their transcription at HCD. Taken together, our data highlight how multiple QS regulators contribute to the pathogenicity of V. parahaemolyticus by precisely controlling the expression of major virulence determinants during different stages of growth.

The role of lamin A/C in mesenchymal stem cell differentiation - Bo Zhang; Yang Yang; Reziwan Keyimu; Jin Hao; Zhihe Zhao; Rui Ye (Journal of Physiology and Biochemistry, 2019)

Characterization of clinical features and outcome for human-to-human transmitted severe fever with thrombocytopenia syndrome - Bei Jia; Weihua Wu; Rui Huang; Guiyang Wang; Peixin Song; Yang Li; Yong Liu; Yali Xiong; Xiaomin Yan; Yingying Hao; Juan Xia; Zhaoping Zhang; et al. (Infectious Diseases, 2018)

Effects of diurnal temperature range on mortality in Hefei city, China - Jing Tang; Chang-chun Xiao; Yu-rong Li; Jun-qing Zhang; Hao-yuan Zhai; Xi-ya Geng; Rui Ding; Jin-xia Zhai (International Journal of Biometeorology, 2018)

Porosity model and air leakage flow field simulation of goaf based on DEM-CFD - Gang Wang; Hao Xu; Mengmeng Wu; Yue Wang; Rui Wang; Xiaoqiang Zhang (Arabian Journal of Geosciences, 2018)

Screening HCV genotype-specific epitope peptides based on conserved sequence analysis and B cell epitope prediction in HCV E2 region - Rui Hua; Xiaoyu Jiang; Lingxia Qi; Shanshan Guan; Ziyu Kuai; Yongbo Qiao; Yan Xu; Xin Gong; Yuhua Shi; Wei Kong; Junqi Niu; Hao Zhang; et al. (Immunologic Research, 2018)

Nature and origin of Triassic igneous activity in the Western Qinling Orogen: the Wenquan composite pluton example - Kun-Feng Qiu; Hao-Cheng Yu; Zong-Yang Gou; Zhi-Lu Liang; Jia-Lin Zhang; Rui Zhu (International Geology Review, 2018)

Precipitation drives the biogeographic distribution of soil fungal community in Inner Mongolian temperate grasslands - Di Wang; Yichao Rui; Kai Ding; Xiaoyong Cui; Yanbin Hao; Li Tang; Zhe Pang; Biao Zhang; Shutong Zhou; Kui Wang; Yanfen Wang (Journal of Soils and Sediments, 2018)

Memantine Can Reduce Ethanol-Induced Caspase-3 Activity and Apoptosis in H4 Cells by Decreasing Intracellular Calcium - Xiaolong Wang; Jiajun Chen; Hongbo Wang; Hao Yu; Changliang Wang; Jiabin You; Pengfei Wang; Chunmei Feng; Guohui Xu; Xu Wu; Rui Zhao; Guohua Zhang (Journal of Molecular Neuroscience, 2017)

Intelligent diagnosis of jaundice with dynamic uncertain causality graph model - Shao-rui Hao; Shi-chao Geng; Lin-xiao Fan; Jia-jia Chen; Qin Zhang; Lan-juan Li (Journal of Zhejiang University-SCIENCE B, 2017)

Efficient Generation of Functionally Active Spinal Cord Neurons from Spermatogonial Stem Cells - Hao Yang; Cuicui Liu; Bo Chen; Jing An; Rui Zhang; Qian Zhang; Jingjing Zhao; Baorong He; Ding-Jun Hao (Molecular Neurobiology, 2017)

Evaluation of serum immunoglobulins concentrations and distributions in vitiligo patients - Yulong Li; Min Yang; Rui Zhang; Wan Liu; Kuo Zhang; Wei Wen; Lang Yi; Qiaoxian Wang; Mingju Hao; Hui Yang; Jianmin Chang; Jinming Li (Immunologic Research, 2016)

Mitochondrial DNA Haplogroup A Decreases the Risk of Drug Addiction but Conversely Increases the Risk of HIV-1 Infection in Chinese Addicts - A-Mei Zhang; Qiu-Xiang Hu; Feng-Liang Liu; Rui Bi; Bi-Qing Yang; Wen Zhang; Hao Guo; Ian Logan; Yong-Tang Zheng; Yong-Gang Yao (Molecular Neurobiology, 2016)

Cadmium Levels in Tissue and Plasma as a Risk Factor for Prostate Carcinoma: a Meta-Analysis - Liang Zhang; Yi Zhu; Rui Hao; Mengmeng Shao; Yunbo Luo (Biological Trace Element Research, 2016)

Circulation and in vivo distribution of duck hepatitis A virus types 1 and 3 in infected ducklings - Shao-Li Lin; Ri-Chao Cong; Rui-Hua Zhang; Jun-Hao Chen; Lin-Lin Xia; Zhi-Jing Xie; Yu Wang; Yan-Li Zhu; Shi-Jin Jiang (Archives of Virology, 2016)

Metabolic responses to Lactobacillus plantarum contamination or bacteriophage treatment in Saccharomyces cerevisiae using a GC–MS-based metabolomics approach - Feng-Xia Cui; Rui-Min Zhang; Hua-Qing Liu; Yan-Feng Wang; Hao Li (World Journal of Microbiology and Biotechnology, 2015)

Flow regime of the three outlets on the south bank of Jingjiang River, China: an impact assessment of the Three Gorges Reservoir for 2003–2010 - Rui Zhang; Shuang-hu Zhang; Wei Xu; Ben-de Wang; Hao Wang (Stochastic Environmental Research and Risk Assessment, 2015)

Curcumin Promotes Cell Cycle Arrest and Inhibits Survival of Human Renal Cancer Cells by Negative Modulation of the PI3K/AKT Signaling Pathway - Hao Zhang; Weili Xu; Baolin Li; Kai Zhang; Yudong Wu; Haidong Xu; Junyong Wang; Jun Zhang; Rui Fan; Jinxing Wei (Cell Biochemistry and Biophysics, 2015)

Transcriptome profiling reveals auxin suppressed anthocyanin biosynthesis in red-fleshed apple callus (Malus sieversii f. niedzwetzkyana) - Xiao-Hao Ji; Rui Zhang; Nan Wang; Long Yang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

DNA methylation level of promoter region of activating transcription factor 5 in glioma - Xiao-min Hua; Juan Wang; Dong-meng Qian; Jing-yi Song; Hao Chen; Xiu-li Zhu; Rui Zhou; Yu-dan Zhao; Xiu-zhi Zhou; Ling Li; Li Zhang; Xu-xia Song; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Dependence of shrub canopy water storage on raindrop size in revegetated desert - Xin-ping Wang; Hao Zhang; Ya-feng Zhang; Rui Hu; Yan-xia Pan (Hydrological Sciences Journal, 2015)

Detection of burned areas from mega-fires using daily and historical MODIS surface reflectance - Rui Zhang; John J. Qu; Yongqiang Liu; Xianjun Hao; Chengquan Huang; Xiwu Zhan (International Journal of Remote Sensing, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Hyperacetylation of Histone H3K9 Involved in the Promotion of Abnormally High Transcription of the gdnf Gene in Glioma Cells - Zheng-Quan Yu; Bao-Le Zhang; Hai-Bo Ni; Ze-Hao Liu; Jian-Cun Wang; Qing-Xian Ren; Jian-Bing Mo; Ye Xiong; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2014)

Snail regulated by PKC/GSK-3β pathway is crucial for EGF-induced epithelial-mesenchymal transition (EMT) of cancer cells - Zong-cai Liu; Xiao-hui Chen; Hai-xing Song; Hong-sheng Wang; Ge Zhang; Hao Wang; Dan-yang Chen; Rui Fang; Hao Liu; Shao-hui Cai; Jun Du (Cell and Tissue Research, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Isolation and functional characterization of a novel rice constitutive promoter - Juan Li; Rong-Fang Xu; Rui-Ying Qin; Hui Ma; Hao Li; Ying-Ping Zhang; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Cell Reports, 2014)

Gabapentin Enhances the Morphine Anti-Nociceptive Effect in Neuropathic Pain via the Interleukin-10-Heme Oxygenase-1 Signalling Pathway in Rats - Yu-Hua Bao; Quan-Hong Zhou; Rui Chen; Hao Xu; Lu-Lu Zeng; Xin Zhang; Wei Jiang; Dong-Ping Du (Journal of Molecular Neuroscience, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

The Neuroprotective Effects of Isoflurane Preconditioning in a Murine Transient Global Cerebral Ischemia–Reperfusion Model: The Role of the Notch Signaling Pathway - Hao-peng Zhang; Yan-yan Sun; Xiao-mei Chen; Li-bang Yuan; Bin-xiao Su; Rui Ma; Rui-ni Zhao; Hai-long Dong; Lize Xiong (NeuroMolecular Medicine, 2014)

Condensation of water vapour on moss-dominated biological soil crust, NW China - XIN-PING WANG; YAN-XIA PAN; RUI HU; YA-FENG ZHANG; HAO ZHANG (Journal of Earth System Science, 2014)

Molecular dynamics-based self-organizing molecular field analysis on 3-amino-6-arylpyrazines as the ataxia telangiectasia mutated and Rad3 related (ATR) protein kinase inhibitors - Hao Luo; Jianyou Shi; Lufei Lu; Feng Wu; Meng Zhou; Xueyan Hou; Wenjuan Zhang; Zhengyu Ding; Rui Li (Medicinal Chemistry Research, 2014)

Potato leafroll virus (PLRV) and Potato virus Y (PVY) influence vegetative growth, physiological metabolism, and microtuber production of in vitro-grown shoots of potato (Solanum tuberosum L.) - Jing-Wei Li; Biao Wang; Xiao-Ming Song; Ren-Rui Wang; Long Chen; Hao Zhang; Zhi-Bo Zhang; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Valproic acid reduces autophagy and promotes functional recovery after spinal cord injury in rats - Hai-Hu Hao; Li Wang; Zhi-Jian Guo; Lang Bai; Rui-Ping Zhang; Wei-Bing Shuang; Yi-Jia Jia; Jie Wang; Xiao-Yu Li; Qiang Liu (Neuroscience Bulletin, 2013)

Heterogeneity of soil surface temperature induced by xerophytic shrub in a revegetated desert ecosystem, northwestern China - YA-FENG ZHANG; XIN-PING WANG; YAN-XIA PAN; RUI HU; HAO ZHANG (Journal of Earth System Science, 2013)

Molecular cloning and functional analysis of a blue light receptor gene MdCRY2 from apple (Malus domestica) - Yuan-Yuan Li; Ke Mao; Cheng Zhao; Xian-Yan Zhao; Rui-Fen Zhang; Hua-Lei Zhang; Huai-Rui Shu; Yu-Jin Hao (Plant Cell Reports, 2013)

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Construction of self-cloning, indigenous wine strains of Saccharomyces cerevisiae with enhanced glycerol and glutathione production - Rui-Ying Hao; Yan-Lin Liu; Zhao-Yue Wang; Bo-run Zhang (Biotechnology Letters, 2012)

Stratigraphic architecture and computer modelling of carbonate platform margin, late ordovician Lianglitage formation, Central Tarim Basin - Hao Li; Changsong Lin; Yanmei Zhang; Rongxi Zhang; Zhifeng Rui; Lili Huang (Journal of Earth Science, 2012)

Effects of Danggui Buxue Tang, a traditional Chinese herbal decoction, on high glucose-induced proliferation and expression of extracellular matrix proteins in glomerular mesangial cells - Hao-Liang Ke; Ying-Wen Zhang; Bi-Fa Zhou; Rui-Tang Zhen (Natural Product Research, 2012)

Implication of genetic variants near TMEM18, BCDIN3D/FAIM2, and MC4R with coronary artery disease and obesity in Chinese: a angiography-based study - Hao Huang; Zhi Zeng; Li Zhang; Rui Liu; Xian Li; Ou Qiang; Yucheng Chen (Molecular Biology Reports, 2012)

Cloning and characterisation of a novel 2,4-dichlorophenol hydroxylase from a metagenomic library derived from polychlorinated biphenyl-contaminated soil - Yang Lu; Ying Yu; Rui Zhou; Wei Sun; Chunyan Dai; Pei Wan; Lanying Zhang; Dongyun Hao; Hejun Ren (Biotechnology Letters, 2011)

Scutellarin exerts its anti-hypertrophic effects via suppressing the Ca2+-mediated calcineurin and CaMKII signaling pathways - Zhen-Wei Pan; Ying Zhang; Dong-Hua Mei; Rui Zhang; Jing-Hao Wang; Xiang-Ying Zhang; Chang-Qing Xu; Yan-Jie Lu; Bao-Feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Fast and dynamic generation of linear octrees for geological bodies under hardware acceleration - Hao Deng; LiQiang Zhang; XianCheng Mao; JingTao Ma; ZhiZhong Kang; JunHuan Peng; XiaoPing Rui; Liu Liu (Science China Earth Sciences, 2010)

Fingerprint analysis of Lingzhi (Ganoderma) strains by high-performance liquid chromatography coupled with chemometric methods - Xian-Min Shi; Jing-Song Zhang; Qing-Jiu Tang; Yan Yang; Rui-Xia Hao; Ying-Jie Pan (World Journal of Microbiology and Biotechnology, 2008)

A Study of Conservation Genetics in Cupressus chengiana, an Endangered Endemic of China, Using ISSR Markers - Bingqing Hao; Wang Li; Mu Linchun; Yao Li; Zhang Rui; Tang Mingxia; Bao Weikai (Biochemical Genetics, 2006)